Resin composition

By using a resin composition including maleimide resin, anionic polymerizable curing agent, an imidazole-based curing catalyst and an inorganic filler, the problems of dielectric loss tangent and insufficient mechanical strength of the existing printed wiring board insulating layer materials are solved. A printed wiring board with low loss and high reliability is achieved.

CN119432072APending Publication Date: 2025-02-14AJINOMOTO CO INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410988871.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-07-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The insulating layer materials of existing printed wiring boards have not reached excellent levels in terms of dielectric loss tangent and mechanical strength, and it is difficult to meet the needs of low loss and high reliability.

Method used

Using a resin composition containing maleimide resin, anionic polymeric curing agent, imidazole-based curing catalyst and inorganic filler material, the curing characteristics of the resin are optimized to achieve low dielectric loss tangent and high The goal of mechanical strength.

Benefits of technology

The reduction of dielectric loss tangent and the improvement of mechanical strength and copper adhesion are achieved, which significantly improves the performance of printed wiring boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004958299500000041
    Figure BDA0004958299500000041
  • Figure BDA0004958299500000061
    Figure BDA0004958299500000061
  • Figure BDA0004958299500000091
    Figure BDA0004958299500000091
Patent Text Reader

Abstract

The present invention addresses the problem of providing a resin composition with which it is possible to obtain a cured product having a low dielectric loss tangent and excellent mechanical strength and copper adhesion. [Solution] A resin composition containing (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, the content of component (D) being 50% by mass or more when the total non-volatile components in the resin composition are taken as 100% by mass, and the content of component (C) being 50% by mass or more when the total non-volatile components in the resin composition are taken as 100% by mass. The maleimide group in the component (A) is 0.1-100 mol equivalent per 1 mol equivalent of the reactive group in the component (B), and the content of the epoxy resin (E) is 0-1 mass% when the non-volatile components other than the component (D) in the resin composition are taken as 100 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition comprising a maleimide resin and an inorganic filler, and further relates to a resin sheet, a printed wiring board and a semiconductor device obtained by using the resin composition. Background Art

[0002] As a manufacturing technology for printed wiring boards, a manufacturing method based on a build-up method in which insulating layers and conductive layers are alternately stacked is known. In the manufacturing method based on the build-up method, the insulating layer is usually formed by curing a resin composition containing a maleimide resin or an inorganic filler.

[0003] For printed wiring boards, a low dielectric loss tangent is required to reduce transmission loss. On the other hand, in order to improve the reliability of printed wiring boards, materials with excellent mechanical strength are also required. However, the resin compositions used to form insulating layers to date do not have a sufficiently low dielectric loss tangent or a sufficiently high mechanical strength (Patent Documents 1 to 3). Prior art literature

[0004] Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2014-521754 Patent Document 2: Japanese Patent No. 6379675 Patent document 3: Japanese Patent No. 6992333. Summary of the invention

[0005] Technical issues to be solved by the invention An object of the present invention is to provide a resin composition capable of obtaining a cured product having a low dielectric loss tangent and excellent mechanical strength and copper adhesion.

[0006] Means for solving technical problems In order to achieve the subject of the present invention, the present inventors conducted intensive research and unexpectedly found that a cured product having low dielectric loss tangent and excellent mechanical strength and copper adhesion can be obtained by using the following resin composition, the resin composition comprising (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst and (D) an inorganic filler, wherein the content of the component (D) is 50% by mass or more when all non-volatile components in the resin composition are set to 100% by mass, the maleimide group of the component (A) is 0.1 to 100 molar equivalents relative to 1 molar equivalent of the reactive group of the component (B), and the content of the epoxy resin (E) is 0 to 1% by mass when the non-volatile components other than the component (D) in the resin composition are set to 100% by mass, thereby completing the present invention.

[0007] That is, the present invention includes the following contents. [1] A resin composition comprising (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, The content of the component (D) is 50% by mass or more, when all nonvolatile components in the resin composition are taken as 100% by mass. The maleimide groups of the component (A) are in an amount of 0.1 to 100 molar equivalents relative to 1 molar equivalent of the reactive groups of the component (B). When the nonvolatile matter other than the (D) component in the resin composition is 100% by mass, the content of the (E) epoxy resin is 0% by mass to 1% by mass. [2] The resin composition according to [1] above, wherein the maleimide group equivalent of the component (A) is 100 g / eq. to 500 g / eq. [3] The resin composition according to [1] or [2] above, wherein component (A) comprises a maleimide resin selected from a maleimide resin having a biphenyl skeleton, a maleimide resin having an indane skeleton, a maleimide resin having a bismaleimide diphenylmethane skeleton, a maleimide resin having a carbon skeleton derived from a dimer acid, and a maleimide resin having an aromatic polyether ketone skeleton. [4] The resin composition according to any one of [1] to [3] above, wherein the content of the component (A) is 30% by mass or more when the non-volatile components other than the component (D) in the resin composition are taken as 100% by mass. [5] The resin composition according to any one of [1] to [4] above, wherein the component (B) comprises an anionic polymerizable curing agent selected from the group consisting of phenolic curing agents, carbodiimide curing agents, amine curing agents, benzoxazine curing agents and active ester curing agents. [6] The resin composition according to any one of [1] to [5] above, wherein the component (B) contains a phenolic curing agent. [7] The resin composition according to any one of [1] to [6] above, wherein the content of the component (B) is 25% by mass or less when the non-volatile components other than the component (D) in the resin composition are taken as 100% by mass. [8] The resin composition according to any one of [1] to [7] above, wherein the mass ratio of the component (B) to the component (A) (component (B) / component (A)) is 0.05 to 1. [9] The resin composition according to any one of [1] to [8] above, wherein the content of the component (C) is 1% to 5% by mass when the non-volatile components other than the component (D) in the resin composition are taken as 100% by mass.

[10] The resin composition according to any one of [1] to [9] above, wherein the component (D) contains silica.

[11] The resin composition according to any one of [1] to

[10] , further comprising (F) a resin containing an ethylenically unsaturated bond.

[12] The resin composition according to any one of [1] to

[11] above, further comprising (G) a thermoplastic resin.

[13] The resin composition according to any one of [1] to

[12] above, wherein the cured product of the resin composition has a breaking strength of 100 MPa or more and an elongation at break of 1.5% or more when the tensile strength is measured according to JIS K7127.

[14] The resin composition according to any one of [1] to

[13] above, wherein a cured product of the resin composition has a glass transition temperature (Tg) of 140° C. or higher.

[15] The resin composition according to any one of [1] to

[14] above, wherein a dielectric loss tangent (Df) of a cured product of the resin composition is 0.004 or less when measured under the conditions of 5.8 GHz and 23°C.

[16] The resin composition according to any one of [1] to

[15] above, wherein a relative dielectric constant (Dk) of a cured product of the resin composition is 3.2 or less when measured under the conditions of 5.8 GHz and 23°C.

[17] A cured product of the resin composition according to any one of [1] to

[16] above.

[18] A resin sheet comprising a support and a resin composition layer formed from the resin composition according to any one of [1] to

[16] above and provided on the support.

[19] A printed wiring board having an insulating layer formed from a cured product of the resin composition according to any one of [1] to

[16] above.

[20] A semiconductor device comprising the printed wiring board described in

[19] above. Effects of the Invention

[0008] According to the resin composition of the present invention, a cured product having a low dielectric loss tangent and excellent mechanical strength and copper adhesion can be obtained. DETAILED DESCRIPTION

[0009] Hereinafter, the present invention will be described in detail based on its preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be implemented with arbitrary changes within the scope of the claims and their equivalents.

[0010] <Resin composition> The resin composition of the present invention comprises (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole curing catalyst and (D) an inorganic filler, wherein the content of the component (D) is 50% by mass or more when all non-volatile components in the resin composition are set to 100% by mass, the maleimide group of the component (A) is 0.1 to 100 molar equivalents relative to 1 molar equivalent of the reactive group of the component (B), and the content of the epoxy resin (E) is 0 to 1% by mass when the non-volatile components other than the component (D) in the resin composition are set to 100% by mass. According to such a resin composition, a cured product having a low dielectric loss tangent and excellent mechanical strength and copper adhesion can be obtained.

[0011] The resin composition of the present invention may further include any component (optionally included component) in addition to (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst and (D) inorganic filler. As the optional component, for example, (E) epoxy resin, (F) resin containing ethylenically unsaturated bonds, (G) thermoplastic resin, (H) free radical polymerization initiator, (I) other additives and (J) organic solvent.

[0012] Hereinafter, each component contained in the resin composition will be described in detail.

[0013] <(A) Maleimide resin> The resin composition of the present invention contains (A) a maleimide resin. The (A) maleimide resin may be used alone or in combination of two or more. The (A) maleimide resin has one or more maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl) in one molecule.

[0014] (A) The maleimide resin may be an aromatic maleimide resin having a maleimide group directly bonded to an aromatic ring or an aliphatic maleimide resin having no maleimide group directly bonded to an aromatic ring, but preferably contains an aromatic maleimide resin.

[0015] The (A) maleimide resin preferably includes a maleimide resin selected from a maleimide resin having a biphenyl skeleton, a maleimide resin having an indane skeleton, a maleimide resin having a bismaleimidediphenylmethane skeleton, a maleimide resin having a carbon skeleton derived from a dimer acid, and a maleimide resin having an aromatic polyetherketone skeleton.

[0016] The carbon skeleton derived from dimer acid refers to a carbon skeleton obtained by removing two terminal carboxyl groups (-COOH) of dimer acid, or by replacing two terminal carboxyl groups (-COOH) with methylene groups (-CH 2 -). Dimer acid is a known compound obtained by dimerizing unsaturated fatty acids (preferably unsaturated fatty acids with 11 to 22 carbon atoms, more preferably unsaturated fatty acids with 14 to 20 carbon atoms, and particularly preferably unsaturated fatty acids with 18 carbon atoms), and its industrial manufacturing process has been roughly standardized in the industry. For dimer acid, a dimer acid with a carbon number of 36 as the main component obtained by dimerizing unsaturated fatty acids with 18 carbon atoms, such as oleic acid and linoleic acid, which are particularly cheap and easily available, can be easily obtained. In addition, for dimer acid, depending on the manufacturing method, degree of purification, etc., it sometimes contains any amount of monomer acid, trimer acid, other polymerized fatty acids, etc. In addition, double bonds remain after the polymerization reaction of unsaturated fatty acids, but in this specification, hydrides whose unsaturation is reduced by further hydrogenation reaction are also included in dimer acid.

[0017] The maleimide resin having a carbon skeleton derived from a dimer acid preferably includes a maleimide resin represented by formula (1).

[0018] [Chemical formula 1]

[0019] [Wherein, n+1 Xs each independently represent a divalent organic group formed by 5 or more backbone atoms selected from carbon atoms, nitrogen atoms (not forming imide), oxygen atoms and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 Xs represents a divalent hydrocarbon group derived from a dimer acid; n Ys each independently represent a tetravalent organic group formed by 5 or more skeleton atoms selected from carbon atoms, nitrogen atoms (not forming imide), oxygen atoms and sulfur atoms, and non-skeleton atoms selected from hydrogen atoms and halogen atoms; n represents an integer greater than or equal to 0 or 1.]

[0020] The n+1 Xs each independently represent a divalent organic group formed by 5 or more (preferably 5 to 200, more preferably 5 to 100, and further preferably 5 to 50) backbone atoms selected from carbon atoms, nitrogen atoms (not forming imide), oxygen atoms, and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 Xs represents a divalent hydrocarbon group derived from a dimer acid.

[0021] The halogen atom is a fluorine atom, a chlorine atom, a bromine atom or an iodine atom.

[0022] The divalent hydrocarbon group derived from a dimer acid refers to a divalent hydrocarbon group obtained by removing two terminal carboxyl groups (-COOH) of a dimer acid, or by replacing two terminal carboxyl groups (-COOH) with methylene groups (-CH 2 -).

[0023] The n+1 Xs may optionally have a divalent organic group other than a divalent hydrocarbon group derived from a dimer acid. When the n+1 Xs are set to 100 mol %, preferably 30 mol % or more are divalent hydrocarbon groups derived from a dimer acid, more preferably 60 mol % or more are divalent hydrocarbon groups derived from a dimer acid, further preferably 90 mol % or more are divalent hydrocarbon groups derived from a dimer acid, and it is particularly preferred that (all) the n+1 Xs are divalent hydrocarbon groups derived from a dimer acid.

[0024] The divalent organic group other than the divalent hydrocarbon group derived from the dimer acid among the n+1 Xs may be a divalent organic group not having an aromatic ring or a divalent organic group having an aromatic ring.

[0025] The n Ys independently represent a tetravalent organic group formed by 5 or more (preferably 5 to 200, more preferably 5 to 100, and further preferably 5 to 50) backbone atoms selected from carbon atoms, nitrogen atoms (not forming imide), oxygen atoms, and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms. The tetravalent organic group represented by Y may be a tetravalent organic group without an aromatic ring or a tetravalent organic group with an aromatic ring.

[0026] In one embodiment, the tetravalent organic group represented by Y is preferably a group selected from the group consisting of formulas (Y1) to (Y5):

[0027] [Chemical formula 2]

[0028] [Wherein, Ring Y 11 , Ring Y 21 , Ring Y 22 , Ring Y 31 , Ring Y 32 , Ring Y 33 , Ring Y41 , Ring Y 42 , Ring Y 43 , Ring Y 44 , Ring Y 51 , Ring Y 52 , Ring Y 53 , Ring Y 54 and Ring Y 55 Each independently represents an aromatic ring optionally having a substituent, or a non-aromatic ring optionally having a substituent; Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d each independently represents a single bond, -C(R y ) 2 -, -O-, -CO-, -S-, -SO-, -SO 2 -, -CONH-, or -NHCO-; R y Each independently represents a hydrogen atom, or an alkyl group optionally substituted by a halogen atom, or two R atoms bonded to the same carbon atom. y are joined together to form a non-aromatic ring optionally having substituents; *Indicates the binding site. ] It should be noted that the two bonding sites on the same ring represented by * are bonding sites to two adjacent carbon atoms on the ring.

[0029] Ring Y 11 , Ring Y 21 , Ring Y 22 , Ring Y 31 , Ring Y 32 , Ring Y 33 , Ring Y 41 , Ring Y 42 , Ring Y 43 , Ring Y 44 , Ring Y 51 , Ring Y 52 , Ring Y 53 , Ring Y 54 and Ring Y 55 Each independently represents an aromatic ring optionally having a substituent, or a non-aromatic ring optionally having a substituent; in one embodiment, it is preferably an aromatic ring optionally having a substituent, more preferably a benzene ring optionally having a substituent, and further preferably a benzene ring optionally substituted by an alkyl group.

[0030] An aromatic ring refers to a ring that follows Hückel's rule and has 4p+2 electrons (p is a natural number) contained in the π electron system on the ring. The aromatic ring may be an aromatic carbocyclic ring having only carbon atoms as ring atoms, or an aromatic heterocyclic ring having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring atoms in addition to carbon atoms. In one embodiment, the aromatic ring is preferably an aromatic carbocyclic ring. In one embodiment, the aromatic ring is preferably an aromatic ring of 5 to 14 members, more preferably an aromatic ring of 6 to 14 members, and further preferably an aromatic ring of 6 to 10 members. Preferred specific examples of the aromatic ring (aromatic carbocyclic ring) include a benzene ring, a naphthalene ring, an anthracene ring, a phenanthrene ring, and the like, more preferably a benzene ring or a naphthalene ring, and particularly preferably a benzene ring.

[0031] A non-aromatic ring refers to a ring other than an aromatic ring having aromaticity as a whole. The non-aromatic ring may be a non-aromatic carbocyclic ring having only carbon atoms as ring atoms, or a non-aromatic heterocyclic ring having, in addition to carbon atoms, heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring atoms. In one embodiment, the non-aromatic ring is preferably a non-aromatic carbocyclic ring. The non-aromatic ring may be a saturated ring or an unsaturated ring. The non-aromatic ring is preferably a 3-21-membered non-aromatic ring, more preferably a 4-17-membered non-aromatic ring, and further preferably a 5-14-membered non-aromatic ring. Preferred specific examples of the non-aromatic ring (non-aromatic carbocyclic ring) include non-aromatic saturated carbocyclic rings of monocyclic systems such as cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and cyclooctane ring; non-aromatic unsaturated carbocyclic rings of monocyclic systems such as cyclobutene ring, cyclopentene ring, cyclohexene ring, cycloheptene ring, cyclooctene ring, cyclopentadiene ring, and cyclohexadiene ring; bicyclo[2.2.1]heptane ring (norbornane ring), bicyclo[4.4.0]decane ring (decalin ring), bicyclo[5.3.0]decane ring, bicyclo[4.3.0]nonane ring (hexahydroindan ring), bicyclo[3.2.1]octane ring, bicyclo[5.4.0]undecane ring, bicyclo[3.3.0]octane ring, bicyclo[3.3.1]nonane ring, tricyclo[5.2.1.0 2,6 ] decane ring (tetrahydrodicyclopentadiene ring), tricyclo[3.3.1.1 3,7 ] decane ring (adamantane ring), tricyclic [6.2.1.0 2,7 ] undecane ring or other non-aromatic saturated carbon rings having two or more ring systems; bicyclo[2.2.1]hept-2-ene ring (norbornene ring), bicyclo[2.2.2]oct-2-ene ring, bicyclo[4.4.0]deca-2-ene ring or other non-aromatic unsaturated carbon rings having two or more ring systems. The non-aromatic ring may be a non-aromatic ring having an aromatic ring condensed in one part. Examples of the non-aromatic ring having an aromatic ring condensed in one part include indane ring, indene ring, tetralin ring, 1,2-dihydronaphthalene ring, 1,4-dihydronaphthalene ring, fluorene ring, 9,10-dihydroanthracene ring, 9,10-dihydrophenanthrene ring, and the like.

[0032] As ring Y 11 , Ring Y 21 , Ring Y 22 , Ring Y 31 , Ring Y 32 , Ring Y 33 , Ring Y 41 , Ring Y 42 , Ring Y 43 , Ring Y 44 , Ring Y 51 , Ring Y 52 , Ring Y 53 , Ring Y 54 and Ring Y 55 The "substituent" in the "aromatic ring optionally having a substituent" and the "non-aromatic ring optionally having a substituent" is not particularly limited, and examples thereof include a halogen atom, -NO 2 , -CN, -COH-, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 、-COOR、-OCOR、-CONH 2 , -CONHR, -CONR 2 , -NHCOR and the like (wherein each R independently represents a monovalent hydrocarbon group).

[0033] A monovalent hydrocarbon group refers to a monovalent hydrocarbon group having only one or more (preferably 1 to 50, more preferably 1 to 20) carbon atoms as backbone atoms and hydrogen atoms as non-backbone atoms. The monovalent hydrocarbon group may be a monovalent saturated hydrocarbon group or a monovalent unsaturated hydrocarbon group. The monovalent hydrocarbon group may or may not have an aromatic structure. Examples of the monovalent hydrocarbon group include alkyl, alkenyl, aryl, aralkyl, and alkylaryl groups.

[0034] The alkyl group refers to a linear, branched and / or cyclic monovalent aliphatic saturated hydrocarbon group. Unless otherwise specified, the alkyl group is preferably an alkyl group having 1 to 14 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, and particularly preferably an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, sec-pentyl, neopentyl, tert-pentyl, hexyl, isohexyl, heptyl, isoheptyl, octyl, isooctyl, tert-octyl, cyclopentyl, cyclohexyl, and cyclohexylmethyl.

[0035] Alkenyl refers to a linear, branched and / or cyclic monovalent aliphatic unsaturated hydrocarbon group having at least one non-aromatic carbon-carbon double bond. Unless otherwise specified, alkenyl is preferably an alkenyl having 2 to 14 carbon atoms, more preferably an alkenyl having 2 to 10 carbon atoms, further preferably an alkenyl having 2 to 6 carbon atoms, and particularly preferably an alkenyl having 2 or 3 carbon atoms. Examples of alkenyl include vinyl, propenyl (allyl, 1-propenyl, isopropenyl), butenyl (1-butenyl, crotyl, methylallyl (metallyl), isocrotyl, etc.), pentenyl (1-pentenyl, etc.), hexenyl (1-hexenyl, etc.), heptenyl (1-heptenyl, etc.), octenyl (1-octenyl, etc.), cyclopentenyl (2-cyclopentenyl, etc.), cyclohexenyl (3-cyclohexenyl), etc.

[0036] The aryl group refers to a monovalent aromatic hydrocarbon group obtained by removing one hydrogen atom from an aromatic carbon ring. Unless otherwise specified, the aryl group is preferably an aryl group having 6 to 14 carbon atoms, and more preferably an aryl group having 6 to 10 carbon atoms. Examples of the aryl group include phenyl, 1-naphthyl, and 2-naphthyl.

[0037] Aralkyl refers to an alkyl group substituted with one or more (preferably one) aryl groups. Unless otherwise specified, the aralkyl group is preferably an aralkyl group having 7 to 15 carbon atoms, and more preferably an aralkyl group having 7 to 11 carbon atoms. Examples of the aralkyl group include benzyl, phenethyl, hydrocinnamyl, α-methylbenzyl, α-cumyl, 1-naphthylmethyl, and 2-naphthylmethyl.

[0038] The alkylaryl group refers to an aryl group substituted with one or more (preferably one) alkyl groups. Unless otherwise specified, the alkylaryl group is preferably an alkylaryl group having 7 to 15 carbon atoms, and more preferably an alkylaryl group having 7 to 11 carbon atoms. Examples of the alkylaryl group include 4-methylphenyl, 3-methylphenyl, 2-methylphenyl, 4-ethylphenyl, 3-ethylphenyl, 2-ethylphenyl, 4-isopropylphenyl, 3-isopropylphenyl, and 2-isopropylphenyl.

[0039] Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d each independently represents a single bond, -C(R y ) 2 -, -O-, -CO-, -S-, -SO-, -SO 2 -, -CONH- or -NHCO-, in one embodiment, preferably a single bond, -C(R y )2 -or-O-.

[0040] R y Each independently represents a hydrogen atom, or an alkyl group optionally substituted by a halogen atom, or two R atoms bonded to the same carbon atom. y Combined together to form a non-aromatic ring optionally having a substituent; in one embodiment, preferably a hydrogen atom, or an alkyl group optionally substituted by a halogen atom, more preferably a hydrogen atom, or a methyl group optionally substituted by a halogen atom, further preferably a hydrogen atom, a methyl group or a trifluoromethyl group, particularly preferably a hydrogen atom or a methyl group.

[0041] As R y The "substituent" in the "non-aromatic ring optionally having a substituent" is not particularly limited, and examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 、-COOR、-OCOR、-CONH 2 , -CONHR, -CONR 2 , -NHCOR and the like (wherein each R independently represents a monovalent hydrocarbon group).

[0042] n represents an integer of 0 or 1 or more; in one embodiment, it is preferably 0 or an integer of 1 to 10, and more preferably 0.

[0043] Examples of commercially available maleimide resins having a carbon skeleton derived from a dimer acid include "BMI-689", "BMI-1500", "BMI-1700", and "BMI-3000J" manufactured by Designer Molecules, and "SLK-6895-T90" manufactured by Shin-Etsu Chemical Co., Ltd.

[0044] The maleimide resin having a bismaleimide diphenylmethane skeleton preferably comprises a maleimide compound represented by formula (2):

[0045] [Chemical formula 3]

[0046] [Wherein, R 10 Each independently represents a hydrogen atom, or an alkyl group optionally substituted by a halogen atom; Ring D each independently represents an aromatic carbon ring which may have a substituent; e represents an integer greater than or equal to 1.] The e units may be the same or different. The maleimide resin having a bismaleimide diphenylmethane skeleton may be used alone or in combination of two or more at any ratio.

[0047] The "substituent" in ring D is not particularly limited, and examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 、-COOR、-OCOR、-CONH 2 , -CONHR, -CONR 2 , -NHCOR and the like (wherein each R independently represents a monovalent hydrocarbon group).

[0048] R 10 Each independently represents a hydrogen atom or an alkyl group which may be substituted by a halogen atom, and is preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a methyl group, and further preferably a hydrogen atom.

[0049] Ring D each independently represents an aromatic ring optionally having a substituent, preferably a benzene ring optionally having a substituent, more preferably a benzene ring optionally substituted with a group selected from an alkyl group and an aryl group, and particularly preferably an (unsubstituted) benzene ring.

[0050] e represents an integer of 1 or more, and is preferably an integer of 1-10.

[0051] As a commercial item of the maleimide resin which has a bismaleimidediphenylmethane skeleton, "BMI-2300" etc. are mentioned, for example, the Yamato Chemical Industry Co., Ltd.

[0052] The maleimide resin having a biphenyl skeleton preferably comprises a maleimide compound represented by formula (3):

[0053] [Chemical formula 4]

[0054] [Wherein, R 20 Each independently represents a hydrogen atom, or an alkyl group optionally substituted by a halogen atom; Ring E, Ring F and Ring G each independently represent an aromatic carbon ring which may have a substituent; f represents an integer greater than or equal to 1.] The f units may be the same or different. The maleimide resin having a biphenyl skeleton may be used alone or in combination of two or more at any ratio.

[0055] The "substituent" in Ring E, Ring F and Ring G is not particularly limited, and examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 、-COOR、-OCOR、-CONH 2 , -CONHR, -CONR 2 , -NHCOR and the like (wherein each R independently represents a monovalent hydrocarbon group).

[0056] R 20 Each independently represents a hydrogen atom or an alkyl group which may be substituted by a halogen atom, and is preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a methyl group, and further preferably a hydrogen atom.

[0057] Ring E, Ring F and Ring G each independently represent an aromatic ring optionally having a substituent, preferably a benzene ring optionally having a substituent, more preferably a benzene ring optionally substituted with a group selected from an alkyl group and an aryl group, and particularly preferably an (unsubstituted) benzene ring.

[0058] f represents an integer of 1 or greater, and is preferably an integer of 1-10.

[0059] Examples of commercially available products of the maleimide resin having a biphenyl skeleton include "MIR-3000-70MT" and "MIR-5000-60T" manufactured by Nippon Kayaku Co., Ltd.

[0060] The maleimide resin having an indane skeleton preferably comprises a maleimide resin represented by formula (4):

[0061] [Chemical formula 5]

[0062] [Wherein, R 30 Each independently represents an alkyl group; Ring H and Ring I each independently represent an aromatic carbon ring which may have a substituent; m represents an integer greater than or equal to 1.] The m units may be the same or different.

[0063] The "substituent" in Ring H and Ring I is not particularly limited, and examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2, -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 、-COOR、-OCOR、-CONH 2 , -CONHR, -CONR 2 , -NHCOR and the like (wherein each R independently represents a monovalent hydrocarbon group).

[0064] R 30 Each independently represents an alkyl group, and in one embodiment, is preferably a methyl group.

[0065] Ring H each independently represents an aromatic ring which may have a substituent, and in one embodiment, is preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with an alkyl group, and even more preferably a benzene ring which may be substituted with an alkyl group.

[0066] Ring I each independently represents an aromatic ring which may have a substituent, and in one embodiment, is preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with an alkyl group, and further preferably an (unsubstituted) benzene ring.

[0067] m represents an integer of 1 or more, and is preferably an integer of 1-20.

[0068] The maleimide resin having an indane skeleton can be produced, for example, by the method described in Japan Invention Association Publication No. 2020-500211 or a method based thereon.

[0069] The maleimide group equivalent of the (A) maleimide resin is preferably 50 g / eq. or more, more preferably 100 g / eq. or more, further preferably 150 g / eq. or more, further more preferably 200 g / eq. or more, further more preferably 250 g / eq. or more, and particularly preferably 300 g / eq. or more, and the upper limit thereof is preferably 2,000 g / eq. or less, more preferably 1,000 g / eq. or less, further preferably 800 g / eq. or less, further more preferably 600 g / eq. or less, further more preferably 500 g / eq. or less, and particularly preferably 450 g / eq. or less. The maleimide group equivalent is the mass of the (A) maleimide resin per 1 molar equivalent of maleimide groups.

[0070] The molecular weight of the maleimide resin (A) is preferably less than 5,000, more preferably less than 3,000, further preferably less than 2,000, further more preferably less than 1,500, further more preferably less than 1,200, and particularly preferably less than 1,000. The lower limit is not particularly limited, and may be, for example, 300 or more, 400 or more, 500 or more, etc.

[0071] The content of (A) maleimide resin in resin composition, when the non-volatile components other than (D) inorganic filler in resin composition are set to 100% by mass, preferably more than 10% by mass, more preferably more than 20% by mass, further preferably more than 25% by mass, further more preferably more than 30% by mass, further more preferably more than 35% by mass, particularly preferably more than 38% by mass, its upper limit is preferably less than 80% by mass, more preferably less than 70% by mass, further preferably less than 60% by mass, further more preferably less than 55% by mass, particularly preferably less than 50% by mass. The content of (A) maleimide resin when all non-volatile components in resin composition are set to 100% by mass is preferably more than 1% by mass, more preferably more than 3% by mass, further preferably more than 5% by mass, further more preferably more than 8% by mass, particularly preferably more than 10% by mass, its upper limit is preferably less than 40% by mass, more preferably less than 35% by mass, further preferably less than 30% by mass, further more preferably less than 25% by mass, particularly preferably less than 22% by mass.

[0072] <(B) Anionic polymerizable curing agent> The resin composition of the present invention contains (B) an anionic polymerizable curing agent. The (B) anionic polymerizable curing agent may have a function of anionically reacting with maleimide resin, epoxy resin, etc. to cure them. The (B) anionic polymerizable curing agent may be used alone or in any combination of two or more.

[0073] Examples of the anionic polymerizable curing agent (B) include phenolic curing agents, carbodiimide curing agents, amine curing agents, benzoxazine curing agents, active ester curing agents, etc. Among them, the anionic polymerizable curing agent (B) preferably includes a phenolic curing agent.

[0074] As the phenolic curing agent, a curing agent having one or more, preferably two or more hydroxyl groups (phenolic hydroxyl groups) bonded to aromatic rings such as a benzene ring or a naphthalene ring in one molecule can be used. As the phenolic curing agent, for example, a phenolic curing agent having a polyphenylene ether structure, a phenolic curing agent having a biphenyl structure (particularly preferably a curing agent containing a 1-propylene group), a phenolic curing agent having a phenolic structure (particularly preferably a curing agent containing a triazine skeleton), etc. can be cited. They can be used alone or in combination of two or more.

[0075] Commercially available products of phenolic curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemicals; "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD-2090", "TD-2090-60M", and "KA-1160" manufactured by DIC; and "SA90" manufactured by SABIC. These may be used alone or in combination of two or more.

[0076] Examples of the carbodiimide curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, for example, aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); biscarbodiimides such as aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), poly(isophoronecarbodiimide); Polycarbodiimides; poly(phenylene carbodiimide), poly(naphthylene carbodiimide), poly(toluene carbodiimide), poly(methyl diisopropyl phenylene carbodiimide), poly(triethyl phenylene carbodiimide), poly(diethyl phenylene carbodiimide), poly(triisopropyl phenylene carbodiimide), poly(diisopropyl phenylene carbodiimide), poly(xylylene carbodiimide), poly(tetramethyl xylylene carbodiimide), poly(methylene diphenylene carbodiimide), poly[methylene bis(methyl phenylene) carbodiimide] and the like aromatic polycarbodiimides.

[0077] Examples of commercially available carbodiimide curing agents include "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07", and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd.; and "Stabaxol P", "Stabaxol P400", and "Hycasyl 510" manufactured by LANXESS.

[0078] As the amine curing agent, there can be mentioned a curing agent having one or more, preferably two or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. Among them, aromatic amines are preferred from the viewpoint of exerting the desired effect of the present invention. The amine curing agent is preferably a primary amine or a secondary amine, more preferably a primary amine.

[0079] Specific examples of the amine curing agent include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, metaphenylenediamine, metaxylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxy phenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. Amine curing agents can be commercially available products, for example, "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., "EPICURE W" manufactured by Mitsubishi Chemical Corporation; "DTDA" manufactured by Sumitomo Seika Chemicals Co., Ltd.; "WA" manufactured by DIC Corporation, etc. These can be used alone or in combination of two or more.

[0080] Examples of the benzoxazine-based curing agent include curing agents having one or more, preferably two or more, benzoxazine structures in one molecule.

[0081] Commercially available benzoxazine curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Co., Ltd., "HFB2006M" manufactured by Showa High Molecular Co., Ltd., and "Pd", "Fa", and "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd. These may be used alone or in combination of two or more.

[0082] As active ester curing agent, generally preferably use phenolic esters, thiophenolic esters, N-hydroxylamine esters, heterocyclic hydroxy compounds and other esters having ester groups with more than 2 high reactive activities in 1 molecule. The active ester compound is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. Especially from the viewpoint of improving heat resistance, active ester curing agent is preferably obtained by carboxylic acid compounds and hydroxy compounds, more preferably by carboxylic acid compounds and phenol compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid etc. can be mentioned. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, and phenolic novolacs. Here, the "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol with one molecule of dicyclopentadiene.

[0083] As the active ester curing agent, specifically, dicyclopentadiene type active ester compounds, naphthalene type active ester compounds containing a naphthalene structure, active ester compounds containing acetylated products of novolac resins, and active ester compounds containing benzoylated products of novolac resins are preferred, among which at least one selected from dicyclopentadiene type active ester compounds and naphthalene type active ester compounds is more preferred. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.

[0084] As for commercially available active ester curing agents, as active ester compounds containing a dicyclopentadiene-type diphenol structure, there are "EXB-9451", "EXB-9460", "EXB-9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", "HPC-8000H-65TM" (manufactured by DIC Corporation); as active ester compounds containing a naphthalene structure, there are "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", "HP C-8150-62T", "EXB-8" (manufactured by DIC Corporation); as the active ester compound containing phosphorus, "EXB9401" (manufactured by DIC Corporation) can be cited, as the active ester compound which is an acetylated product of linear phenolic resin, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be cited, as the active ester compound which is a benzoylated product of linear phenolic resin, "YLH1026", "YLH1030", "YLH1048" (manufactured by Mitsubishi Chemical Corporation) can be cited, as the active ester compound containing vinylphenyl and naphthalene structures, "PC1300-02-65MA" (manufactured by Air Water Corporation) can be cited, etc.

[0085] The reactive group equivalent of the anionic polymerizable curing agent (B) is preferably 3,000 g / eq. or less, more preferably 2,000 g / eq. or less, further preferably 1,000 g / eq. or less, and particularly preferably 800 g / eq. or less, and its lower limit is preferably 40 g / eq. or more, more preferably 60 g / eq. or more, further preferably 80 g / eq. or more, and particularly preferably 100 g / eq. or more. The reactive group equivalent is the mass of the anionic polymerizable curing agent (B) per 1 molar equivalent of reactive groups. The so-called reactive group refers to a functional group that undergoes anionic reaction with maleimide resin, epoxy resin, etc. For example, if it is a phenol-based curing agent, it refers to a phenolic hydroxyl group, if it is a carbodiimide-based curing agent, it refers to a carbodiimide group (-N=C=N-), if it is an amine-based curing agent, it refers to an amino group, if it is a benzoxazine-based curing agent, it refers to a benzoxazine group, and if it is an active ester-based curing agent, it refers to a reactive ester group (ester of phenolic hydroxyl group).

[0086] The content of the anionic polymerizable curing agent (B) in the resin composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, further more preferably 1% by mass or more, particularly preferably 3% by mass or more, when the non-volatile components other than the inorganic filler (D) in the resin composition are set to 100% by mass, and the upper limit is preferably 60% by mass or less, more preferably 50% by mass or less, further preferably 40% by mass or less, further more preferably 30% by mass or less, further more preferably 25% by mass or less, and particularly preferably 20% by mass or less. The content of the anionic polymerizable curing agent (B) when the total non-volatile components in the resin composition are set to 100% by mass is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.1% by mass or more, further more preferably 0.15% by mass or more, and particularly preferably 0.2% by mass or more, and the upper limit is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, further more preferably 10% by mass or less, and particularly preferably 8% by mass or less.

[0087] The mass ratio of the (B) anionic polymerizable curing agent to the (A) maleimide resin in the resin composition (content of the (B) component / content of the (A) component) is preferably 0.02 or more, more preferably 0.05 or more, further preferably 0.07 or more, particularly preferably 0.08 or more, and the upper limit is preferably 2 or less, more preferably 1 or less, further preferably 0.8 or less, and particularly preferably 0.6 or less.

[0088] In the resin composition, the amount of maleimide groups of the maleimide resin (A) is 0.1 molar equivalents or more, preferably 0.3 molar equivalents or more, more preferably 0.5 molar equivalents or more, further preferably 0.6 molar equivalents or more, and particularly preferably 0.7 molar equivalents or more, relative to 1 molar equivalent of the reactive groups of the anionic polymerizable curing agent (B). The upper limit is 100 molar equivalents or less, preferably 80 molar equivalents or less, more preferably 60 molar equivalents or less, further preferably 50 molar equivalents or less, further more preferably 40 molar equivalents or less, further more preferably 30 molar equivalents or less, and particularly preferably 20 molar equivalents or less. The reactive group refers to a functional group that undergoes anionic reaction with maleimide resin, epoxy resin, etc. For example, if it is a phenol-based curing agent, it refers to a phenolic hydroxyl group, if it is a carbodiimide-based curing agent, it refers to a carbodiimide group (-N=C=N-), if it is an amine-based curing agent, it refers to an amino group, if it is a benzoxazine-based curing agent, it refers to a benzoxazine group, and if it is an active ester-based curing agent, it refers to a reactive ester group (ester of phenolic hydroxyl group).

[0089] <(C) Imidazole Curing Catalyst> The resin composition of the present invention contains (C) an imidazole curing catalyst. The (C) imidazole curing catalyst has a function as a catalyst for accelerating the curing of maleimide resin, epoxy resin, etc. The (C) imidazole curing catalyst may be used alone or in combination of two or more.

[0090] (C) The imidazole curing catalyst is preferably a compound represented by formula (C), a salt thereof, an isocyanuric acid adduct thereof, or an adduct thereof with an epoxy resin:

[0091] [Chemical formula 6]

[0092] [Wherein, R 1 , R 3 and R 4 Each independently represents a hydrogen atom, -CN, -NO 2 , -OH, -NH 2 、-CHO、-R a 、-OR a 、-NHR a 、-NR a 2 、-COR a 、-COOR a 、-OCOR a ,-CONHR a 、-NHCOR a 、-SR a or -SO 2 R a ; R 2 Represents a hydrogen atom or -R a ; R 1 and R 2 , or R 2 and R 3 may be combined together to form a nitrogen-containing heterocyclic ring which may optionally have a substituent; R 3 and R 4 may be combined together to form an aromatic ring which may optionally have a substituent; R a Each independently represents a monovalent hydrocarbon group which may have a substituent.] Examples of the salt include carboxylates and the like, and specific examples thereof include trimellitic acid salts and the like.

[0093] As R 1 and R 2 , or R 2 and R 3The "nitrogen-containing heterocyclic ring optionally having a substituent" formed and R 3 and R 4 The "substituent" in the "aromatic ring optionally having a substituent" is not particularly limited, and examples thereof include -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 、-COOR、-OCOR、-CONH 2 , -CONHR, -CONR 2 , -NHCOR and the like (wherein each R independently represents a monovalent hydrocarbon group).

[0094] The "substituent" in the "monovalent hydrocarbon group optionally having a substituent" of R is not particularly limited, and examples thereof include -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R", -COR', -OR', -SR', -SOR', -SO 2 R', -NHR', -N(R') 2 、-COOR'、-OCOR'、-CONH 2 、-CONHR'、-CON(R') 2 , -NHCOR', -NHCONHR' and other monovalent substituents (wherein R' independently represents (1) optionally selected from -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , aryl and alkylaryl, (2) optionally selected from -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , aryl, and alkylaryl, (3) optionally selected from -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , alkyl, alkenyl, aryl, aralkyl and alkylaryl; or (4) optionally substituted with -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , alkyl, alkenyl, aryl, aralkyl and alkylaryl, wherein R" represents a heteroaryl group optionally selected from -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , alkyl, alkenyl, aryl, aralkyl and alkylaryl. ).

[0095] A heteroaryl group refers to a monovalent group formed by removing one hydrogen atom from an aromatic heterocyclic ring having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring atoms in addition to carbon atoms. Unless otherwise specified, the heteroaryl group is preferably a 5- to 14-membered heteroaryl group, and particularly preferably a 5- to 10-membered heteroaryl group. Examples of the heteroaryl group include furanyl, thienyl, pyrrolyl, pyrazolyl, oxazolyl, isoxazolyl, thiazolyl, imidazolyl, pyridyl, pyridazinyl, pyrimidinyl, pyrazinyl, triazinyl (e.g., 1,3,5-triazin-2-yl, etc.), and the like.

[0096] A nitrogen-containing heterocycle refers to a heterocycle having at least a carbon atom and a nitrogen atom as ring atoms, and further having heteroatoms other than nitrogen atoms such as oxygen atoms and sulfur atoms as ring atoms. The nitrogen-containing heterocycle may be a monocyclic nitrogen-containing heterocycle, a bicyclic nitrogen-containing heterocycle, or a tricyclic nitrogen-containing heterocycle, but in one embodiment, a monocyclic nitrogen-containing heterocycle is preferred. In one embodiment, the nitrogen-containing heterocycle is preferably 4 to 14 members, and more preferably 5 to 10 members. As preferred specific examples of nitrogen-containing heterocycles, monocyclic nitrogen-containing non-aromatic heterocycles such as pyrrolidine ring, imidazolidine ring, imidazoline ring, pyrazolidine ring, pyrazoline ring, oxazolidine ring, oxazoline ring, thiazolidine ring, and thiazoline ring can be cited; bicyclic nitrogen-containing non-aromatic heterocycles such as indoline ring and dihydrobenzimidazole ring can be cited.

[0097] Specific examples of the (C) imidazole curing catalyst include 2-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1-methyl-2-ethylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1-isobutyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole (e.g., “CUREZOL 2P4MZ” manufactured by Shikoku Chemical Industries, Ltd.), 1-benzyl-2-methylimidazole, 1-benzyl-2-ethylimidazole, 1-benzyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-methylimidazole (e.g., “CUREZOL 2MZ-CN” manufactured by Shikoku Chemical Industries, Ltd.), 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole (e.g., “CUREZOL 2P4MZ” manufactured by Shikoku Chemical Industries, Ltd.), 2E4MZ-CN”), 1-(2-cyanoethyl)-2-undecylimidazole (e.g., “CUREZOL C11Z-CN” manufactured by Shikoku Chemical Industries, Ltd.), 1-(2-cyanoethyl)-2-undecylimidazole trimellitate, 1-(2-cyanoethyl)-2-phenylimidazole (e.g., “CUREZOL 2PZ-CN” manufactured by Shikoku Chemical Industries, Ltd.), 1-aminoethyl-2-methylimidazole, 1-(cyanoethylaminoethyl)-2-methylimidazole, 1-(2-cyanoethyl)-2-methylimidazole trimellitate (e.g., “CUREZOL 2MZ-CNS” manufactured by Shikoku Chemical Industries, Ltd.), 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole trimellitate (e.g., “CUREZOL 2E4MZ-CNS”), 1-(2-cyanoethyl)-2-undecyl imidazole trimellitate (e.g., “CUREZOL C11Z-CNS” manufactured by Shikoku Chemical Industry Co., Ltd.), 1-(2-cyanoethyl)-2-phenyl imidazole trimellitate (e.g., “CUREZOL 2PZ-CNS” manufactured by Shikoku Chemical Industry Co., Ltd.), 1-benzyl-2-phenyl imidazole (e.g., “CUREZOL 1B2PZ” manufactured by Shikoku Chemical Industry Co., Ltd.), 1-benzyl-2-phenyl imidazole trimellitate (e.g., “CUREZOL 1B2PZ-S”), 2,4-diamino-6-(2-ethyl-4-methyl-1-imidazolyl)ethyl-1,3,5-triazine, 2,4-diamino-6-(2-methyl-1-imidazolyl)ethyl-1,3,5-triazine (for example, “CUREZOL 2MZ-A” and “CUREZOL 2MZA-PW” manufactured by Shikoku Chemical Industry Co., Ltd.), 2,4-diamino-6-(2-undecyl-1-imidazolyl)ethyl-1,3,5-triazine (for example, “CUREZOL C11Z-A” manufactured by Shikoku Chemical Industry Co., Ltd.), 2,4-diamino-6-(2-ethyl-4-methyl-1-imidazolyl)ethyl-1,3,5-triazine5-triazine (for example, "CUREZOL 2E4MZ-A" manufactured by Shikoku Chemical Industry Co., Ltd.), 2-methylimidazole-isocyanuric acid adduct (for example, "CUREZOL 2MZ-OK" manufactured by Shikoku Chemical Industry Co., Ltd.), 2-phenylimidazole-isocyanuric acid adduct (for example, "CUREZOL 2PZ-OK" manufactured by Shikoku Chemical Industry Co., Ltd.), 2,4-diamino-6-(2-methyl-1-imidazolyl)ethyl-1,3,5-triazine-isocyanuric acid adduct (for example, "CUREZOL 2E4MZ-A" manufactured by Shikoku Chemical Industry Co., Ltd.), 2MA-OK”), 4-formyl imidazole, 2-phenyl-4-formyl imidazole, 4,4'-bis(2-ethyl-5-methylimidazolyl)methane (e.g., “CUREZOL2E4MZ·BIZ” manufactured by Shikoku Chemical Industry Co., Ltd.), 2-phenyl-4-methyl-5-hydroxymethyl imidazole (e.g., “CUREZOL2P4MHZ” manufactured by Shikoku Chemical Industry Co., Ltd.), 2-phenyl-4,5-bis(hydroxymethyl)imidazole (e.g., “CUREZOL 2PHZ”, “CUREZOL 2PHZ-PW” manufactured by Shikoku Chemical Industry Co., Ltd.), 1-cyanoethyl-2-phenyl-4,5-bis(cyanoethoxymethyl)imidazole (e.g., “CUREZOL The imidazole compound may be an imidazole compound such as 1-dodecyl-2-methyl-3-benzylimidazole, N,N'-(2-methyl-1-imidazolylethyl) adipamide, 1,3-dibenzyl-2-methylimidazole, 4,5-bis(hydroxymethyl)-2-phenylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, or an adduct of an imidazole compound and an epoxy resin (e.g., "CUREDUCT P-0505" manufactured by Shikoku Chemical Industries, Ltd., "JER CURE P200H50" manufactured by Mitsubishi Chemical Corporation, etc.).

[0098] The molecular weight of the (C) imidazole curing catalyst is preferably 2,000 or less, more preferably 1,000 or less, further preferably 700 or less, further more preferably 500 or less, particularly preferably 400 or less, and the lower limit thereof is not particularly limited, and may be, for example, 80 or more, 100 or more, etc.

[0099] The melting point of the imidazole curing catalyst (C) is preferably 120°C or higher, more preferably 140°C or higher, further preferably 160°C or higher, particularly preferably 180°C or higher, and the upper limit is preferably 245°C or lower, more preferably 220°C or lower, further preferably 210°C or lower, particularly preferably 200°C or lower.

[0100] The content of (C) imidazole curing catalyst in resin composition, when the non-volatile components other than (D) inorganic filler in resin composition are set to 100% by mass, preferably 0.001% by mass or more, more preferably 0.01% by mass or more, further preferably 0.1% by mass or more, further more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, its upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, further more preferably 7% by mass or less, particularly preferably 5% by mass or less. The content of (C) imidazole curing catalyst when all non-volatile components in resin composition are set to 100% by mass, preferably 0.001% by mass or more, more preferably 0.01% by mass or more, further preferably 0.05% by mass or more, further more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, its upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, further more preferably 2% by mass or less, particularly preferably 1.5% by mass or less.

[0101] The mass ratio of the (C) imidazole-based curing catalyst to the (A) maleimide resin in the resin composition (content of the (C) component / content of the (A) component) is preferably 0.005 or more, more preferably 0.01 or more, further preferably 0.02 or more, particularly preferably 0.03 or more, and the upper limit is preferably 0.5 or less, more preferably 0.3 or less, further preferably 0.2 or less, and particularly preferably 0.15 or less.

[0102] <(D) Inorganic fillers> The resin composition of the present invention contains (D) an inorganic filler. The (D) inorganic filler is contained in the resin composition in the form of particles.

[0103] As the material of (D) inorganic filler, an inorganic compound is used. As the material of (D) inorganic filler, for example, silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc., can be cited. Among them, silica, alumina or aluminosilicate is preferred, and silica is particularly preferred. As silica, for example, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. can be cited. In addition, as silica, spherical silica is preferred. (D) The inorganic filler may be used alone or in combination of two or more at any ratio.

[0104] (D) Commercially available products of the inorganic filler include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Yaduma Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; "Cellspheres" and "MGH-005" manufactured by Pacific Cement Co., Ltd.; and "Hipresica FH" manufactured by Ube Exsymo Co., Ltd.

[0105] (D) The average particle size of the inorganic filler is not particularly limited, preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, further preferably 1 μm or less, and particularly preferably 0.8 μm or less. (D) The lower limit of the average particle size of the inorganic filler is not particularly limited, preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. (D) The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on Mie scattering theory. Specifically, a particle size distribution of an inorganic filler can be prepared on a volume basis by a laser diffraction scattering particle size distribution measuring device, and the median diameter can be measured as the average particle size. The sample can be measured by weighing 100 mg of an inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the sample with ultrasound for 10 minutes. For the measurement sample, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source is set to blue and red, and the particle size distribution of the volume basis of the inorganic filler is measured by the flow cell method, and the average particle size is calculated as the median particle size by the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba Manufacturing Co., Ltd. can be cited.

[0106] (D) The specific surface area of ​​the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of ​​the inorganic filler (D) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 50m 2 / g or less, more preferably 30m 2 / g or less, particularly preferably 10m 2 The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen on the surface of a sample using a specific surface area measuring device (MAcsorb HM-1210 manufactured by Mountech) according to the BET method and calculating the specific surface area using the BET multipoint method.

[0107] (D) The inorganic filler may be a solid inorganic filler having an average porosity of 0 volume % (preferably solid silica, solid alumina, solid aluminosilicate), or a hollow inorganic filler having an average porosity exceeding 0 volume % (preferably hollow silica, hollow alumina, hollow aluminosilicate).

[0108] The average porosity of the hollow inorganic filling material is preferably 90% by volume or less, more preferably 80% by volume or less. The lower limit of the average porosity of the hollow inorganic filling material is not particularly limited, for example, it is more than 0% by volume, 1% by volume or more, preferably 5% by volume or more, more preferably 10% by volume or more, and further preferably 15% by volume or more. The average porosity P (volume %) of the inorganic filling material is defined as the volume-based ratio (total volume of pores / volume of particles) of "the total volume of one or more pores existing inside the particle" relative to "the volume of the entire particle based on the outer surface of the particle", for example, using the measured value D of the actual density of the inorganic filling material. M (g / cm 3 ), and the theoretical value D of the material density of the material forming the inorganic filler T (g / cm 3 ), calculated using the following formula (I).

[0109] [Mathematical formula 1]

[0110] The actual density of the inorganic filler can be measured, for example, using a true density measuring device. Examples of the true density measuring device include ULTRAPYCNOMETER 1000 manufactured by QUANTACHROME Co., Ltd. As the measuring gas, for example, nitrogen gas is used.

[0111] From the viewpoint of improving moisture resistance and dispersibility, (D) inorganic filler is preferably treated with a surface treatment agent. As the surface treatment agent, for example, fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. can be cited. In addition, the surface treatment agent can be used alone or in any combination of two or more.

[0112] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBE903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM103” (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM-4803” (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd., and “KBM-7103” (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.

[0113] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment performed by the surface treatment agent is preferably within a specified range. Specifically, 100% by mass of the inorganic filler is preferably surface treated with 0.2% by mass to 5% by mass of the surface treatment agent, more preferably with 0.2% by mass to 3% by mass, and further preferably with 0.3% by mass to 2% by mass.

[0114] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of ​​the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the melt viscosity of the resin composition layer or the melt viscosity in the form of a sheet from increasing, the amount of carbon per unit surface area of ​​the inorganic filler is preferably 1.0 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2 the following.

[0115] (D) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added as a solvent to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid component, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. can be used.

[0116] The content of the (D) inorganic filler in the resin composition is 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, further preferably 65% ​​by mass or more, further more preferably 70% by mass or more, particularly preferably 72% by mass or more, when the total non-volatile components in the resin composition are set to 100% by mass, and the upper limit is preferably 90% by mass or less, more preferably 85% by mass or less, further preferably 80% by mass or less, and particularly preferably 75% by mass or less.

[0117] The mass ratio of the (D) inorganic filler to the (A) maleimide resin in the resin composition (component (D) / component (A)) is not particularly limited, but is preferably 1.5 or more, more preferably 2 or more, further preferably 2.3 or more, and particularly preferably 2.5 or more. The upper limit is preferably 25 or less, more preferably 20 or less, further preferably 15 or less, further more preferably 10 or less, and particularly preferably 8 or less.

[0118] The total content of (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst and (D) inorganic filler in the resin composition is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 75% by mass or more, further more preferably 78% by mass or more, and particularly preferably 80% by mass or more, when all non-volatile components in the resin composition are set to 100% by mass.

[0119] <(E) Epoxy resin> The resin composition of the present invention may contain (E) an epoxy resin in an amount of 0 to 1% by mass relative to 100% by mass of nonvolatile components excluding (D) the inorganic filler. (E) The epoxy resin is a curable resin having an epoxy group and an epoxy equivalent of 5,000 g / eq. or less.

[0120] (E) Epoxy resins include, for example, bixylenol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidyl ester epoxy resins, cresol epoxy resins, Novolac epoxy resin, phenol aralkyl epoxy resin, biphenyl epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane epoxy resin, cyclohexanedimethanol epoxy resin, naphthylene ether epoxy resin, trimethylol epoxy resin, tetraphenylethane epoxy resin, isocyanurate epoxy resin, phenolphthalimidine epoxy resin, etc. (E) The epoxy resin may be used alone or in combination of two or more.

[0121] In the resin composition of the present invention, as (E) epoxy resin, it is preferred to include an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and usually 100% by mass or less relative to 100% by mass of the epoxy resin (E).

[0122] (E) The epoxy resin includes an epoxy resin that is liquid at a temperature of 20°C (hereinafter sometimes referred to as "liquid epoxy resin") and an epoxy resin that is solid at a temperature of 20°C (hereinafter sometimes referred to as "solid epoxy resin"). The resin composition of the present invention may contain only a liquid epoxy resin, only a solid epoxy resin, or both a liquid epoxy resin and a solid epoxy resin as the epoxy resin, and it is particularly preferred to contain both a liquid epoxy resin and a solid epoxy resin.

[0123] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.

[0124] As the liquid epoxy resin, preferred are glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexanedimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure.

[0125] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene-based epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825", and "EPIKOTE "828EL" (bisphenol A type epoxy resin); "jER807", "1750" (bisphenol F type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation; "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "EX-991L" manufactured by ChemteX (an epoxy resin containing an alkylene oxide skeleton and a butadiene skeleton); "CELLOXIDE2021P" manufactured by Daicel Corporation (an alicyclic epoxy resin with an ester skeleton); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins with a butadiene structure); "ZX1658" and "ZX1658GS" manufactured by Nippon Steel Chemical Materials Co., Ltd. (liquid 1,4-glycidylcyclohexane type epoxy resins); "EG-280" manufactured by Osaka Gas Chemical Co., Ltd. (an epoxy resin containing a fluorene structure); "EX-201" manufactured by Nagase ChemteX (cyclic aliphatic glycidyl ether), etc.

[0126] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.

[0127] As solid epoxy resins, preferred are biphenylol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, naphthol novolac-type epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthyl ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, phenol aralkyl-type epoxy resins, tetraphenylethane-type epoxy resins, and phenol benzopyrrolidone-type epoxy resins.

[0128] Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; " EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthyl ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. ); "ESN475V", "ESN4100V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "YX4000H", "YX4000", "YX4000HK", "YL7890" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "WHR991S" (phenol benzopyrrolone type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., etc. These may be used alone or in combination of two or more.

[0129] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin (E), their mass ratio (liquid epoxy resin:solid epoxy resin) is preferably 10:1 to 1:50, more preferably 5:1 to 1:20, further preferably 2:1 to 1:10, and particularly preferably 1:1 to 1:3.

[0130] (E) The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., further preferably 70 g / eq. to 1,000 g / eq., and further more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per 1 equivalent of epoxy group. The epoxy equivalent can be measured according to JIS K 7236.

[0131] (E) The weight average molecular weight (Mw) of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).

[0132] The content of the epoxy resin (E) in the resin composition is 0% to 1% by mass, when the non-volatile components other than the inorganic filler (D) in the resin composition are set to 100% by mass. In one embodiment, it is preferably 0% to 0.8% by mass, more preferably 0% to 0.7% by mass, further preferably 0% to 0.5% by mass, further more preferably 0% to 0.3% by mass, further more preferably 0% to 0.1% by mass, further more preferably 0% to 0.01% by mass, and particularly preferably 0% to 0.001% by mass.

[0133] In one embodiment, from the viewpoint of taking into account copper bonding strength and mechanical strength, it is preferred to include a specific amount of (E) epoxy resin. In this embodiment, the content of (E) epoxy resin in resin combination is preferably more than 0.001 mass %, more preferably more than 0.01 mass %, further preferably more than 0.1 mass %, particularly preferably more than 0.3 mass %, and its upper limit is less than 1 mass %, preferably less than 0.8 mass %, more preferably less than 0.7 mass %. When the content of epoxy resin exceeds 1 mass %, mechanical strength is reduced, and when it exceeds 5 mass %, in addition to copper bonding strength and mechanical strength, there is also a tendency that dielectric loss tangent is impaired.

[0134] <(F) Resin containing ethylenically unsaturated bonds> The resin composition of the present invention may further include (F) a resin containing an ethylenically unsaturated bond as an arbitrary component (optionally contained component). The resin containing an ethylenically unsaturated bond (F) described here is a component other than the substances belonging to the (A) maleimide resin and (B) anionic polymerizable curing agent described above. As the resin containing an ethylenically unsaturated bond (F), for example, polystyrene resins having an ethylenically unsaturated group, benzocyclobutene resins having an ethylenically unsaturated group, etc. can be cited.

[0135] The polystyrene resin having an ethylenically unsaturated group may preferably be a polystyrene resin including a repeating structural unit represented by formula (F1) and a repeating structural unit represented by formula (F2).

[0136] [Chemical formula 7]

[0137] [Wherein, R a1 , R a2 and R a3 each independently represents a hydrogen atom or an alkyl group; R a4 Each independently represents an alkyl group; a represents an integer from 0 to 5.]

[0138] [Chemical formula 8]

[0139] [Wherein, R b1 , R b2 , R b3 , R b5 , R b6 and R b7 each independently represents a hydrogen atom or an alkyl group; R b4 Each independently represents an alkyl group; b represents an integer from 0 to 4.]

[0140] The benzocyclobutene resin having an ethylenically unsaturated group is a compound containing an ethylenically unsaturated group having one or more benzocyclobutene rings, preferably two or more benzocyclobutene rings. In one embodiment, the benzocyclobutene resin having an ethylenically unsaturated group further preferably has an organosiloxane skeleton. As the organosiloxane skeleton, for example, dialkylsiloxane skeletons such as dimethylsiloxane skeletons, diarylsiloxane skeletons such as diphenylsiloxane skeletons, etc. can be cited, preferably dialkylsiloxane skeletons, particularly preferably dimethylsiloxane skeletons.

[0141] The benzocyclobutene resin having an ethylenically unsaturated group is preferably a resin represented by formula (F3):

[0142] [Chemical formula 9]

[0143] [Wherein, R c1 and R c3 Each independently represents a hydrogen atom or a monovalent hydrocarbon group; R c2 and R c4Each independently represents a monovalent hydrocarbon group; c each independently represents an integer from 0 to 3; d each independently represents an integer greater than or equal to 1.]

[0144] R c1 and R c3 Each independently represents a hydrogen atom or a monovalent hydrocarbon group, preferably a hydrogen atom or an alkyl group, and particularly preferably a hydrogen atom. c2 and R c4 Each independently represents a monovalent hydrocarbon group, preferably an alkyl group or an aryl group, and particularly preferably an alkyl group. c each independently represents an integer of 0 to 3, and preferably 0. d each independently represents an integer greater than 1, and preferably an integer of 1 to 3, and more preferably 1.

[0145] As a commercial product of the benzocyclobutene resin which has an ethylenically unsaturated group, "CYCLOTENE 3022" etc. are mentioned, for example, the Dow Chemical Company.

[0146] The weight average molecular weight (Mw) of the resin (F) containing an ethylenically unsaturated bond is preferably 500 or more, more preferably 1,000 or more, further preferably 2,000 or more, particularly preferably 3,000 or more, and the upper limit is preferably 100,000 or less, more preferably 70,000 or less, further preferably 60,000 or less, particularly preferably 50,000 or less.

[0147] The content of the resin (F) containing an ethylenically unsaturated bond in the resin composition, when the non-volatile components other than the (D) inorganic filler in the resin composition are set to 100% by mass, can be, for example, 0% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 1% by mass or more, further more preferably 5% by mass or more, further more preferably 10% by mass or more, and particularly preferably 15% by mass or more, and the upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 55% by mass or less, further more preferably 50% by mass or less, and particularly further preferably 45% by mass or less. The content of the resin (F) containing an ethylenically unsaturated bond when all non-volatile components in the resin composition are set to 100% by mass may be, for example, 0% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 1% by mass or more, further more preferably 3% by mass or more, particularly preferably 4% by mass or more, and the upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, further preferably 20% by mass or less, further more preferably 15% by mass or less, and particularly preferably 10% by mass or less.

[0148] The total content of (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst, (D) inorganic filler, (E) epoxy resin and (F) resin containing ethylenically unsaturated bonds in the resin composition is preferably 80% by mass or more, more preferably 70% by mass or more, further preferably 75% by mass or more, further more preferably 80% by mass or more, further more preferably 85% by mass or more, and particularly preferably 90% by mass or more. The upper limit of the total content of (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst, (D) inorganic filler, (E) epoxy resin and (F) resin containing ethylenically unsaturated bonds in the resin composition is not particularly limited, for example, it can be 100% by mass or less.

[0149] <(G) Thermoplastic resin> The resin composition of the present invention may further contain (G) a thermoplastic resin as an optional component. The (G) thermoplastic resin described here refers to a component other than the (B) anionic polymerizable curing agent and (E) epoxy resin described above.

[0150] As (G) thermoplastic resin, for example, polymers containing oxazoline groups, polyimide resins, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyamide-imide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene oxide resins, polycarbonate resins, polyetheretherketone resins, polyester resins, etc. can be cited. In one embodiment, (G) thermoplastic resin preferably includes a thermoplastic resin selected from polymers containing oxazoline groups, polyimide resins, and phenoxy resins, more preferably includes a thermoplastic resin selected from polyimide resins and phenoxy resins, and particularly preferably includes a phenoxy resin. In addition, thermoplastic resins can be used alone or in combination of two or more.

[0151] The oxazoline group-containing polymer can be prepared by, for example, mixing 2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 4,4,5-trimethyl-2-isopropenyl-2-oxazoline, 2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, The invention relates to a method for preparing the oxazoline-containing polymerizable oxazoline compound (a monomer containing a vinyl oxazoline skeleton) by polymerization of oxazoline compounds such as oxazoline-2-vinyl-2-oxazoline and 4,4,5-trimethyl-2-vinyl-2-oxazoline. Other monomers such as styrene monomers such as styrene, α-methylstyrene, 4-methylstyrene, 3-methylstyrene, 2-methylstyrene, 4-ethylstyrene, 4-tert-butylstyrene, p-divinylbenzene, and m-divinylbenzene can also be copolymerized as needed. Specific examples of polymers containing oxazoline groups include "PX-3-RP-61" manufactured by Nippon Shokubai Co., Ltd.

[0152] Specific examples of the polyimide resin include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "RIKACOAT SN20" and "RIKACOAT PN20" manufactured by Shin Nippon Chemical Co., Ltd.

[0153] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, phenolic skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0154] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290" and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0155] Examples of the polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, preferably polyvinyl butyral resin. Specific examples of the polyvinyl acetal resin include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0156] Examples of the polyolefin resin include ethylene copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-methyl acrylate copolymers; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymers.

[0157] Examples of the polybutadiene resin include a resin containing a hydrogenated polybutadiene skeleton, a polybutadiene resin containing a hydroxyl group, a polybutadiene resin containing a phenolic hydroxyl group, a polybutadiene resin containing a carboxyl group, a polybutadiene resin containing an acid anhydride group, a polybutadiene resin containing an epoxy group, a polybutadiene resin containing an isocyanate group, a polybutadiene resin containing a urethane group, and a polyphenylene ether-polybutadiene resin.

[0158] Specific examples of polyamideimide resins include "VYLOMAX HR11NN" and "VYLOMAX HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamideimide resins include modified polyamideimides such as "KS9100" and "KS9300" (polyamideimide containing a polysiloxane skeleton) manufactured by Hitachi Chemical Co., Ltd.

[0159] Specific examples of the polyethersulfone resin include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. and the like.

[0160] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0161] Specific examples of the polyphenylene ether resin include "NORYL SA90" manufactured by SABIC, etc. Specific examples of the polyetherimide resin include "Ultem" manufactured by GE, etc.

[0162] As polycarbonate resins, there can be mentioned hydroxyl-containing carbonate resins, phenolic hydroxyl-containing carbonate resins, carboxyl-containing carbonate resins, anhydride-containing carbonate resins, isocyanate-containing carbonate resins, urethane-containing carbonate resins, etc. As specific examples of polycarbonate resins, there can be mentioned "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002", "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Co., Ltd., "C-1090", "C-2090", "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd., etc. As specific examples of polyetheretherketone resins, there can be mentioned "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd., etc.

[0163] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0164] From the viewpoint of significantly obtaining the effects of the present invention, the weight average molecular weight (Mw) of the (G) thermoplastic resin is preferably 5,000 or more, more preferably 8,000 or more, further preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, further preferably 60,000 or less, and particularly preferably 50,000 or less.

[0165] The content of the (G) thermoplastic resin in the resin composition, when the non-volatile components other than the (D) inorganic filler in the resin composition are taken as 100% by mass, can be, for example, 0% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, further more preferably 1% by mass or more, further more preferably 2% by mass or more, particularly preferably 3% by mass or more, and particularly preferably 4% by mass or more, and the upper limit thereof is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, further more preferably 40% by mass or less, and particularly preferably 35% by mass or less. The content of the (G) thermoplastic resin when the total non-volatile components in the resin composition are set to 100% by mass may be, for example, 0% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, further more preferably 1% by mass or more, particularly preferably 1.3% by mass or more, and the upper limit is preferably 35% by mass or less, more preferably 30% by mass or less, further preferably 25% by mass or less, further more preferably 20% by mass or less, and particularly preferably 15% by mass or less.

[0166] The total content of (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst, (D) inorganic filler, (E) epoxy resin, (F) resin containing ethylenically unsaturated bonds and (G) thermoplastic resin in the resin composition is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, further more preferably 95% by mass or more, further more preferably 98% by mass or more, and particularly preferably 99% by mass or more. The upper limit of the total content of (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst, (D) inorganic filler, (E) epoxy resin, (F) resin containing ethylenically unsaturated bonds and (G) thermoplastic resin in the resin composition is not particularly limited, for example, it can be 100% by mass or less.

[0167] <(H) Radical Polymerization Initiator> The resin composition of the present invention may contain (H) a radical polymerization initiator as an optional component. The (H) radical polymerization initiator is preferably a thermal polymerization initiator that generates radicals when heated. The (H) radical polymerization initiator may be used alone or in any combination of two or more.

[0168] (H) As a radical polymerization initiator, a peroxide radical polymerization initiator, an azo radical polymerization initiator, etc. are mentioned, for example. Among them, a peroxide radical polymerization initiator is preferable.

[0169] Examples of the peroxide-based radical polymerization initiator include hydroperoxide compounds such as 1,1,3,3-tetramethylbutyl hydroperoxide; dialkyl peroxide compounds such as tert-butyl isopropyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; dilauroyl peroxide, didecanoyl peroxide, dicyclohexyl peroxydicarbonate, bis(4-tert-butylcyclohexyl)peroxide Peroxy diacyl compounds such as oxidized dicarbonates; peroxy ester compounds such as tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, 1,1-dimethylpropyl 2-ethylperoxyhexanoate, tert-butyl 2-ethylperoxyhexanoate, tert-butyl 3,5,5-trimethylperoxyhexanoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxymaleate, etc.; etc.

[0170] Examples of the azo radical polymerization initiator include azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, and 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile; and azobis(2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide, 2,2'-azobis[2-methyl-N-[1,1-bis( Azo amide compounds such as 2,2'-azobis[2-methyl-N-[2-(1-hydroxybutyl)]-propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(2-methylpropionamide) dihydrate, 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide); alkylazo compounds such as 2,2'-azobis(2,4,4-trimethylpentane) and 2,2'-azobis(2-methylpropane); etc.

[0171] (H) Examples of commercially available products of the radical polymerization initiator include “PERBUTYL C”, “PERBUTYL A”, “PERBUTYL P”, “PERBUTYL L”, “PERBUTYL O”, “PERBUTYL ND”, “PERBUTYL Z”, “PERBUTYL I”, “PERCUMYL P”, “PERCUMYL D”, “PERHEXYL D”, “PERHEXYL A”, “PERHEXYL I”, “PERHEXYL Z”, “PERHEXYL ND”, “PERHEXYL O”, and “PERHEXYL PV” manufactured by NOF Corporation.

[0172] The content of the (H) radical polymerization initiator in the resin composition is not particularly limited. When the non-volatile component in the resin composition is set to 100% by mass, it is preferably 1% by mass or less, more preferably 0.5% by mass or less, further preferably 0.1% by mass or less, further more preferably 0.05% by mass or less, and particularly preferably 0.03% by mass or less. The lower limit is not particularly limited. When the non-volatile component in the resin composition is set to 100% by mass, it can be, for example, 0% by mass or more, 0.0001% by mass or more, preferably 0.0005% by mass or more, more preferably 0.001% by mass or more, further preferably 0.005% by mass or more, and particularly preferably 0.01% by mass or more.

[0173] <(I) Other additives> The resin composition of the present invention may further contain any additives. Examples of such additives include curing catalysts other than imidazole curing catalysts, such as phosphorus curing catalysts, urea curing catalysts, guanidine curing catalysts, metal curing catalysts, and amine curing catalysts; organic fillers such as rubber particles; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as Benton (bentonite) and montmorillonite; defoamers such as silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resin defoamers; ultraviolet absorbers such as benzotriazole ultraviolet absorbers; and adhesion enhancers such as urea silane. ; Adhesion-imparting agents such as triazole-based adhesion-imparting agents, tetrazole-based adhesion-imparting agents, and triazine-based adhesion-imparting agents; antioxidants such as hindered phenol-based antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (such as melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (such as antimony trioxide); dispersants such as phosphate-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers, etc. (I) Other additives may be used alone or in combination of two or more in any ratio. The content of (I) other additives can be appropriately determined by those skilled in the art.

[0174] <(J) Organic solvents> The resin composition of the present invention may further contain any organic solvent. As (J) organic solvent, a known organic solvent may be used appropriately, and its type is not particularly limited. As (J) organic solvent, for example: ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, anisole, etc.; alcohol solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, carbitol acetate (ethyl diglycol Ether ester solvents such as acetate, diethylene glycol monoethyl ether acetate), γ-butyrolactone, methyl methoxypropionate, etc.; ester alcohol solvents such as methyl lactate, ethyl lactate, methyl 2-hydroxyisobutyrate, etc.; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, diethylene glycol monobutyl ether (butyl carbitol), etc.; amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc.; sulfoxide solvents such as dimethyl sulfoxide, etc.; nitrile solvents such as acetonitrile and propionitrile, etc.; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, methylcyclohexane, etc.; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, trimethylbenzene, etc. (J) The organic solvent may be used alone or in combination of two or more in any ratio.

[0175] The content of (J) organic solvent in the varnish-like resin composition before drying is not particularly limited, and when all the components in the resin composition are set to 100% by mass, for example, it is 40% by mass or less, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 8% by mass or less, and particularly preferably 6% by mass or less. The lower limit of the content of (J) organic solvent in the varnish-like resin composition before drying, when all the components in the resin composition are set to 100% by mass, can be 0% by mass, or it can be greater than 0% by mass. The content of (J) organic solvent in the dried resin composition forming the resin composition layer in the resin sheet is not particularly limited, and when all the components in the resin composition are set to 100% by mass, it is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 2% by mass or less, and particularly preferably 1% by mass or less. The lower limit of the content of (J) organic solvent in the dried resin composition forming the resin composition layer in the resin sheet, when all the components in the resin composition are set to 100% by mass, can be 0% by mass, or it can be greater than 0% by mass.

[0176] <Method for producing resin composition> The resin composition of the present invention can be prepared by, for example, adding and mixing (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole curing catalyst, (D) inorganic filler, (E) epoxy resin as required, (F) resin containing ethylenically unsaturated bonds as required, (G) thermoplastic resin as required, (H) free radical polymerization initiator as required, (I) other additives as required, and (J) organic solvent as required in any preparation container in any order and / or partially or entirely at the same time. In addition, in the process of adding each component to mix, the temperature can be appropriately set, and heating and / or cooling can be performed temporarily or all the time. In addition, it is also possible to stir or vibrate the resin composition in the process of adding and mixing or afterwards, for example, using a stirring device or an oscillating device such as a stirrer to make it uniformly dispersed. In addition, deaeration can be performed under low pressure conditions such as under vacuum while stirring or vibrating.

[0177] <Characteristics of Resin Composition> The resin composition of the present invention comprises (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole curing catalyst and (D) an inorganic filler, wherein the content of the component (D) is 50% by mass or more when all non-volatile components in the resin composition are 100% by mass, the content of the component (D) is 0.1% by mass to 100% by mass relative to 1 molar equivalent of the reactive group of the component (B), and the content of the epoxy resin (E) is 0% by mass to 1% by mass when the non-volatile components other than the component (D) in the resin composition are 100% by mass. According to such a resin composition, a cured product having a low dielectric loss tangent and excellent mechanical strength and copper adhesion can be obtained.

[0178] The cured product of the resin composition of the present invention has excellent mechanical strength. For example, as described in Test Example 3 described later, the breaking strength of the cured product of the resin composition when the tensile strength is measured according to JIS K7127 is preferably 50 MPa or more, more preferably 70 MPa or more, further preferably 80 MPa or more, further more preferably 90 MPa or more, further more preferably 95 MPa or more, particularly preferably 100 MPa or more, and particularly preferably 105 MPa or more. For example, as described in Test Example 3 described later, the breaking elongation of the cured product of the resin composition when the tensile strength is measured according to JIS K7127 is preferably 0.5% or more, more preferably 1.0% or more, further preferably 1.3% or more, further more preferably 1.5% or more, and particularly preferably 1.7% or more.

[0179] The dielectric loss tangent of the cured product of the resin composition of the present invention is low. For example, as described in Test Example 1 described later, the dielectric loss tangent (Df) of the cured product of the resin composition measured at 5.8 GHz and 23° C. is preferably 0.01 or less, more preferably 0.007 or less, further preferably 0.005 or less, further more preferably 0.004 or less, and particularly preferably 0.0035 or less. The lower limit of the dielectric loss tangent (Df) is not particularly limited, and for example, it can be 0.0001 or more.

[0180] The cured product of the resin composition of the present invention has excellent copper adhesion (copper foil peel strength). For example, after laminating copper foil on the cured product as described in the following Test Example 4, the copper foil peel strength based on JIS C 6481 calculated from the load when the copper foil is pulled in the vertical direction and peeled off is preferably 0.2 kgf / cm or more, more preferably 0.3 kgf / cm or more, further preferably 0.4 kgf / cm or more, further more preferably 0.45 kgf / cm or more, and particularly preferably 0.5 kgf / cm or more.

[0181] In one embodiment, the cured product of the resin composition of the present invention may have a low relative dielectric constant. In one embodiment, for example, as described in Test Example 1 described later, the relative dielectric constant (Dk) of the cured product of the resin composition measured at 5.8 GHz and 23°C may be preferably 5.0 or less, more preferably 4.5 or less, further preferably 4.0 or less, further more preferably 3.5 or less, further more preferably 3.3 or less, particularly preferably 3.2 or less, and particularly preferably 3.1 or less. The lower limit of the relative dielectric constant (Dk) is not particularly limited, for example, it may be 1.0 or more.

[0182] In one embodiment, the cured product of the resin composition of the present invention may have a high glass transition temperature (Tg). In one embodiment, for example, the glass transition temperature (Tg) when measured as described in the following Test Example 2 may be preferably 100°C or more, more preferably 120°C or more, further preferably 130°C or more, further more preferably 140°C or more, further more preferably 150°C or more, and particularly preferably 160°C or more.

[0183] <Application of resin composition> The resin composition of the present invention can be used as a resin composition for insulating purposes, particularly as a resin composition for forming an insulating layer. Specifically, the resin composition of the present invention can be suitably used as: a resin composition for forming an insulating layer (a resin composition for forming an insulating layer for forming a conductor layer), wherein the insulating layer is an insulating layer for forming a conductor layer (including a rewiring layer), and the conductor layer is formed on the insulating layer. In addition, in the printed wiring board described later, the resin composition of the present invention can be suitably used as a resin composition for forming the insulating layer of a printed wiring board (a resin composition for forming an insulating layer of a printed wiring board). In addition, the resin composition of the present invention can be widely used in sheet-like laminated materials such as resin sheets, prepregs, solder resists, bottom filling materials, chip bonding materials, semiconductor sealing materials, hole-filling resins, component embedding resins, etc., which require the use of resin compositions.

[0184] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can also be suitably used as a resin composition for a rewiring forming layer as an insulating layer for forming a rewiring layer (resin composition for forming a rewiring forming layer), and a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When manufacturing a semiconductor chip package, a rewiring layer can be further formed on the sealing layer. (1) a step of laminating a temporary fixing film on a substrate, (2) a step of temporarily fixing the semiconductor chip on a temporary fixing film, (3) a step of forming a sealing layer on a semiconductor chip, (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip, (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off, and (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0185] Furthermore, since the resin composition of the present invention provides an insulating layer having good component embedding properties, it can be preferably used when the printed wiring board is a component-embedded wiring board.

[0186] <Sheet-like laminated material> The resin composition of the present invention can be used by coating in a varnish state, but is usually preferably used in the form of a sheet-like laminate containing the resin composition in industrial terms.

[0187] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.

[0188] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed of the resin composition of the present invention.

[0189] From the viewpoint of thinning the printed wiring board and providing a cured product having excellent insulation properties even if the cured product of the resin composition is a thin film, the thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be set to 5 μm or more, 10 μm or more, etc.

[0190] Examples of the support include films made of plastic materials, metal foils, and release papers, and films and metal foils made of plastic materials are preferred.

[0191] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0192] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal of copper or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).

[0193] The surface of the support to be in contact with the resin composition layer may be subjected to matte treatment, corona treatment, or antistatic treatment.

[0194] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent for the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins and silicone resins can be cited. The support with a release layer can use commercially available products, for example: PET film having a release layer with an alkyd resin-based release agent as the main component, "SK-1", "AL-5", "AL-7" made by Lintec, "LUMIRROR T60" made by Toray, "Purex" made by Teijin, "Unipeel" made by UNITIKA, etc.

[0195] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the entire thickness of the support with a release layer is preferably in the above range.

[0196] In one embodiment, the resin sheet may further include an arbitrary layer as required. As the arbitrary layer, for example, a protective film selected according to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress the attachment of garbage or the formation of damage on the surface of the resin composition layer.

[0197] The resin sheet can be manufactured, for example, as follows: a liquid (varnish-like) resin composition is directly used, or a liquid (varnish-like) resin composition is prepared by dissolving the resin composition in an organic solvent, and the liquid (varnish-like) resin composition is applied to a support using a die coater or the like, and then dried to form a resin composition layer.

[0198] Examples of the organic solvent include the same organic solvents as those described as components of the resin composition. The organic solvent may be used alone or in combination of two or more.

[0199] Drying can be carried out by known methods such as heating and hot air blowing. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the organic solvent in the resin composition. For example, when using a resin composition containing 30% to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.

[0200] The resin sheet can be stored by being wound into a roll. When the resin sheet has a protective film, the resin sheet can be used by peeling off the protective film.

[0201] In one embodiment, the prepreg is formed by impregnating the resin composition of the present invention into a sheet-like fiber base material.

[0202] The sheet-like fiber substrate used in the prepreg is not particularly limited, and glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. can be used as materials commonly used as prepreg substrates. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.

[0203] The prepreg can be produced by a known method such as a hot melt method or a solvent method.

[0204] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.

[0205] The sheet-like laminated material of the present invention can be suitably used to form an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).

[0206] <Printed wiring board> The printed wiring board of the present invention includes an insulating layer formed of a cured product obtained by curing the resin composition of the present invention.

[0207] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet and by a method including the following steps (I) and (II): (I) a step of laminating a resin sheet on the inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate; and (II) a step of curing (eg, thermally curing) the resin composition layer to form an insulating layer.

[0208] The "inner substrate" used in step (I) refers to a component that becomes a substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, a thermosetting polyphenylene ether substrate, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of a substrate is sometimes referred to as an "inner circuit substrate". In addition, an intermediate product to be further formed with an insulating layer and / or a conductor layer when manufacturing a printed wiring board is also included in the "inner substrate" referred to in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.

[0209] The lamination of the inner substrate and the resin sheet can be performed, for example, by heat-pressing the resin sheet to the inner substrate from the support body side. As a member for heat-pressing the resin sheet to the inner substrate (hereinafter also referred to as a "heat-pressing member"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It should be noted that it is preferred that the heat-pressing member is not directly pressed on the resin sheet, but is pressed through an elastic material such as heat-resistant rubber so that the resin sheet fully follows the surface unevenness of the inner substrate.

[0210] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination, the heating and pressing temperature is preferably 60°C to 160°C, more preferably 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. Lamination is preferably implemented under reduced pressure conditions of 26.7hPa or less.

[0211] Lamination can be performed by a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.

[0212] After lamination, the laminated resin sheet can be smoothed by, for example, pressing the heating and pressing member from the support body side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing treatment can be the same as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed by a commercially available laminator. It should be noted that the lamination and smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.

[0213] The support may be removed between step (I) and step (II), or may be removed after step (II).

[0214] In step (II), the resin composition layer is cured (eg, thermally cured) to form an insulating layer composed of a cured product of the resin composition. The curing conditions of the resin composition layer are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.

[0215] For example, the thermal curing conditions of the resin composition layer vary depending on the type of the resin composition, etc. In one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and further preferably 170° C. to 210° C. The curing time may be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and further preferably 15 minutes to 100 minutes.

[0216] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature of 50°C to 120°C, preferably 60°C to 115°C, more preferably 70°C to 110°C, for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0217] When manufacturing a printed wiring board, the step of (III) opening holes in the insulating layer, the step of (IV) roughening the insulating layer, and the step of (V) forming a conductor layer can be further implemented. These steps (III) to step (V) can be implemented according to various methods known to those skilled in the art used in the manufacture of printed wiring boards. It should be noted that when the support body is removed after step (II), the removal of the support body can be implemented between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, as needed, the formation of the insulating layer and the conductor layer of steps (II) to step (V) can be repeatedly implemented to form a multilayer wiring board.

[0218] In other embodiments, the printed wiring board of the present invention can be produced using the above-mentioned prepreg. The production method is basically the same as that in the case of using a resin sheet.

[0219] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and vias in the insulating layer. Step (III) can be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.

[0220] Step (IV) is a step of roughening the insulating layer. Usually, in step (IV), contamination is also removed. The steps and conditions of the roughening treatment are not particularly limited, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be used. For example, the insulating layer can be roughened by swelling treatment using a swelling solution, roughening treatment using an oxidant, and neutralization treatment using a neutralizing solution in sequence.

[0221] The swelling liquid used in the roughening treatment is not particularly limited, and examples thereof include alkaline solutions, surfactant solutions, and the like. Alkaline solutions are preferred, and sodium hydroxide solutions and potassium hydroxide solutions are more preferred as the alkaline solutions. Commercially available swelling liquids include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, and for example, it can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred that the insulating layer be immersed in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.

[0222] The oxidant used in the roughening treatment is not particularly limited, and an alkaline permanganate solution obtained by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide can be cited. The roughening treatment using an oxidant such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidants, alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited.

[0223] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction solution Securiganth P" manufactured by Atotech Japan Co., Ltd.

[0224] The treatment with a neutralizing solution can be performed by immersing the treated surface subjected to the roughening treatment with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of operability, etc., a method in which the object subjected to the roughening treatment with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.

[0225] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is not particularly limited, but is preferably less than 500nm, more preferably less than 400nm, and more preferably less than 300nm. The lower limit is not particularly limited, for example, it can be more than 1nm, more than 2nm, etc. In addition, the root mean square roughness (Rq) of the insulating layer surface after roughening treatment is preferably less than 500nm, more preferably less than 400nm, and more preferably less than 300nm. The lower limit is not particularly limited, for example, it can be more than 1nm, more than 2nm, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0226] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (for example, a nickel-chromium alloy, a copper-nickel alloy and a copper-titanium alloy) can be cited. Among them, from the viewpoints of versatility, cost, ease of pattern formation, etc., of the formation of the conductor layer, preferably a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy, more preferably a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, and further preferably a single metal layer of copper.

[0227] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of nickel-chromium alloy.

[0228] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.

[0229] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the insulating layer can be plated by a conventionally known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed by a semi-additive method. An example of forming a conductor layer by a semi-additive method is shown below.

[0230] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, so that a conductor layer having a desired wiring pattern can be formed.

[0231] In other embodiments, the conductor layer can be formed using a metal foil. When a metal foil is used to form a conductor layer, step (V) is preferably implemented between step (I) and step (II). For example, after step (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented using a vacuum lamination method. The lamination conditions can be the same as those described for step (I). Next, step (II) is implemented to form an insulating layer. Then, using the metal foil on the insulating layer, a conductor layer with a desired wiring pattern can be formed using existing known techniques such as a subtractive method and a modified semi-additive method.

[0232] The metal foil can be produced by a known method such as electrolysis or rolling. Commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Metals, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.

[0233] <Semiconductor Device> The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be produced using the printed wiring board of the present invention.

[0234] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes). Example

[0235] The present invention is specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, below, unless otherwise clearly stated, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass", respectively. The temperature condition when the temperature is not particularly specified is room temperature (23° C.), and the pressure condition when the pressure is not particularly specified is atmospheric pressure (1 atm).

[0236] <Synthesis Example 1: Synthesis of Maleimide A> Maleimide A (m=1.47, Mw / Mn=1.81) represented by the following formula was synthesized by the same method as in Synthesis Example 1 of Japan Invention Patent Publication No. 2020-500211 to obtain a MEK solution of maleimide resin (non-volatile content 62% by mass).

[0237] [Chemical formula 10]

[0238] <Synthesis Example 2: Synthesis of Phenol B> In a 1L reaction vessel equipped with a thermometer, a stirrer, and a cooling tube, 410g of methanol, 48.0g of sodium hydroxide, and 205.0g of biphenol were added, and 91.8g of allyl chloride was added dropwise at 40°C over 3 hours while paying attention to the generation of heat. Then, the temperature was raised to the temperature at which methanol refluxed (about 60°C), and an allyl etherification reaction was carried out for 4 hours. Next, after washing with water to remove salts, the temperature was raised to 180°C, and a transfer reaction was carried out for 10 hours. After the transfer reaction, the temperature was lowered to 100°C, 205.0g of butanol was added to dissolve the resin, and 70.5g of potassium hydroxide was added, and an allylation reaction was carried out at 115°C for 6 hours. Then, the mixture was washed with water and concentrated to obtain "phenol B" (an allylic form of biphenol).

[0239] [Chemical formula 11]

[0240] <Synthesis Example 3: Synthesis of Ester Compound C> 89 parts by mass of o-allylphenol, 110 parts by mass of dicyclopentadiene-phenol copolymer resin (softening point 85°C, hydroxyl equivalent of about 165 g / eq.), and 1000 parts by mass of toluene were added to a reaction container, and dissolved while the container was replaced with nitrogen under reduced pressure. Next, 135 parts by mass of isophthaloyl chloride was added and dissolved. Next, 0.5 g of tetrabutylammonium bromide was added, and 309 g of a 20% aqueous sodium hydroxide solution was added dropwise over 3 hours while the container was purged with nitrogen. At this time, the temperature in the system was controlled below 60°C. Then, the mixture was stirred for 1 hour to react. After the reaction was completed, the reactants were separated and the water layer was removed. This operation was repeated until the pH of the water layer reached 7, and toluene and the like were distilled off under heating and reduced pressure conditions to obtain an ester compound C (unsaturated bond equivalent of 428 g / eq.) containing an aromatic ester skeleton and an unsaturated bond.

[0241] <Synthesis Example 4: Synthesis of Vinyl Resin D> 3.0 mol (390.6 g) of divinylbenzene, 1.8 mol (229.4 g) of ethylvinylbenzene, 10.2 mol (1066.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were placed in a 5.0 L reactor, and 600 mmol of diethyl ether complex of boron trifluoride was added at 70°C to react for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed 3 times with pure water, and the polymer was recovered by decompression and devolatilization at 60°C. The obtained substance was weighed, and 896.7 g of vinyl compound D was confirmed. The weight average molecular weight (Mw) of vinyl compound D was 41300.

[0242] <Synthesis Example 5: Synthesis of Polyimide E> Prepare a 500mL detachable flask with a moisture quantitative receiver connected to a reflux condenser, a nitrogen inlet tube and a stirrer. Add 20.3g of 4,4'-oxydiphthalic anhydride (ODPA), 200g of γ-butyrolactone, 20g of toluene and 29.6g of 5-(4-aminophenoxy)-3-[4-(4-aminophenoxy)phenyl]-1,1,3-trimethylindane to the flask, stir at 45°C for 2 hours under a nitrogen stream, and react. Next, the reaction solution was heated, and the condensation water was removed azeotropically with toluene under a nitrogen stream while being maintained at about 160°C. It was confirmed that a specified amount of water was accumulated in the moisture quantitative receiver, and that water outflow was no longer observed. After confirmation, the reaction solution was further heated and stirred at 200°C for 1 hour. Then, the mixture was cooled to obtain a polyimide solution (non-volatile content: 20% by mass) containing polyimide E having a 1,1,3-trimethylindane skeleton. The weight average molecular weight of polyimide E was 12,000.

[0243] <Examples 1 to 5, Comparative Examples 1 to 5: Preparation of resin compositions> Each component was weighed according to the mixing ratio by mass in Table 1, and 10 parts of MEK and 10 parts of cyclohexanone were further mixed and uniformly dispersed using a high-speed rotary mixer to prepare a varnish-like resin composition. The details of each component in Table 1 are as follows.

[0244] (A) Maleimide resin MIR-3000-70MT: maleimide resin with biphenyl skeleton, maleimide group equivalent weight 393 g / eq., toluene solution containing 70% by mass of nonvolatile components, manufactured by Nippon Kayaku Co., Ltd. Maleimide A: Maleimide resin having an indane skeleton, maleimide group equivalent weight 428 g / eq., the resin synthesized in Synthesis Example 1 · BMI-2300: Maleimide resin having a bismaleimide diphenylmethane skeleton, maleimide group equivalent weight 179 g / eq., manufactured by Yamato Chemical Industries, Ltd. SLK-6895-T90: maleimide resin having a carbon skeleton derived from dimer acid, maleimide group equivalent 345 g / eq., toluene solution with a nonvolatile content of 90% by mass, manufactured by Shin-Etsu Chemical Co., Ltd.

[0245] (B) Anionic polymerizable curing agent LA-3018-50P: phenolic curing agent, functional group equivalent 151 g / eq., 1-methoxy-2-propanol solution with a non-volatile content of 50% by mass, manufactured by DIC Corporation ·ALP-d: Benzoxazine curing agent, functional group equivalent 257g / eq., manufactured by Shikoku Chemical Industry Co., Ltd. SA90: phenolic curing agent, functional group equivalent 800g / eq., manufactured by SABIC Phenol B: phenolic curing agent, functional group equivalent 133 g / eq., the substance synthesized in Synthesis Example 2 Ester compound C: active ester curing agent, functional group equivalent 214 g / eq., toluene solution with a solid content of 70%, manufactured by DIC Corporation V-03: Carbodiimide curing agent, functional group equivalent 216 g / eq., non-volatile matter 50% by mass toluene solution, manufactured by Nisshinbo Chemical Co., Ltd. WA: Amine curing agent, functional group equivalent 45g / eq., manufactured by DIC Corporation

[0246] (C) Imidazole curing catalyst ·1B2PZ: 1-benzyl-2-phenylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd. ·2P4MZ: 2-phenyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd. ·C11Z-A: 2,4-diamino-6-(2-undecyl-1-imidazolyl)ethyl-1,3,5-triazine, manufactured by Shikoku Chemical Industry Co., Ltd.

[0247] (D) Inorganic filling materials SO-C2: Spherical silica surface-treated with an amine alkoxysilane compound ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, made by Yaduma UFP-30: Spherical silica surface-treated with an amine alkoxysilane compound ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.3 μm, specific surface area 30.7 m 2 / g, made by Denka Hipresica FH: Hollow silica surface-treated with an amine alkoxysilane compound ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, porosity 30-50%, manufactured by Ube Exsymo Co., Ltd.

[0248] (E) Epoxy resin HP-4032-SS: Naphthalene-based epoxy resin, epoxy equivalent 144 g / eq., manufactured by DIC Corporation

[0249] (F) Resins containing ethylenically unsaturated bonds Vinyl resin D: polystyrene resin having ethylenically unsaturated groups, the resin synthesized in Synthesis Example 4, non-volatile content 50% by mass CYCLOTENE 2022: Benzocyclobutene resin with ethylenically unsaturated groups, manufactured by The Dow Chemical Company

[0250] (G) Thermoplastic resin ·PX-3-RP-61: Oxazoline-containing polymer, manufactured by Nippon Shokubai Co., Ltd. YX7553BH30: phenoxy resin, 1:1 solution of MEK and cyclohexanone with a nonvolatile content of 30% by mass, manufactured by Mitsubishi Chemical Corporation Polyimide E: polyimide resin, synthesized in Synthesis Example 5, non-volatile content 20% by mass

[0251] (H) Radical Polymerization Initiator PERHEXYL D: Peroxide-based free radical polymerization initiator, di-tert-hexyl peroxide, manufactured by NOF Corporation

[0252] <Test Example 1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> (1) Preparation of Resin Sheet A Having a Resin Composition Layer Thickness of 40 μm As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) having a release layer was prepared. On the release layer of the support, the varnish-like resin composition obtained in the examples and comparative examples was evenly applied in such a manner that the thickness of the resin composition layer after drying was 40 μm. Then, the resin composition was dried at 80°C to 100°C (average 90°C) for 2 minutes to obtain a resin sheet A comprising a support and a resin composition layer.

[0253] (2) Preparation of solidified material The obtained resin sheet A was cured in an oven at 190° C. for 90 minutes. The support was peeled off by removing the resin sheet A from the oven to obtain a cured product of the resin composition layer.

[0254] (3) Determination of relative dielectric constant (Dk) and dielectric loss tangent (Df) The cured product was cut into pieces of 80 mm in length and 2 mm in width, and the dielectric constant and dielectric loss tangent (Dk value, Df value) were measured by the cavity perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. and 90° C. using "HP8362B" manufactured by Agilent Technologies. The measurement was performed on two test pieces, and the average value was calculated.

[0255] <Test Example 2: Measurement of glass transition temperature (Tg)> The cured product obtained in Test Example 1 (2) was cut into test pieces of about 5 mm in width and about 15 mm in length, and a thermomechanical analysis was performed using a thermomechanical analyzer ("Thermo Plus TMA8310" manufactured by Rigaku Corporation) by a tensile load method. After the test piece was mounted on the above-mentioned device, the thermal expansion coefficient (ppm) was measured twice continuously under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. Based on the value of the thermal expansion coefficient from 25°C to 150°C in the second measurement, the average linear expansion coefficient (ppm / °C) was calculated, and in the second measurement, the glass transition temperature (Tg; °C) was calculated.

[0256] <Test Example 3: Measurement of breaking strength and breaking elongation> The cured product obtained in Test Example 1 (2) was subjected to tensile strength measurement using a tensile tester "RTC-1250A" manufactured by Orientec Corporation, and the breaking strength and breaking elongation at 23° C. were measured. The measurement was carried out in accordance with JIS K 7127. The measurement was performed 5 times, and the average of the top 3 values ​​from the largest to the smallest was calculated.

[0257] <Test Example 4: Measurement of Copper Foil Peel Strength> (1) Base treatment of copper foil The shiny surface of the electrolytic copper foil (Mitsui Mining and Co., Ltd. "3EC-III", thickness 35 μm) was etched 1 μm with a microetchant (MEC "CZ8101") to roughen the copper surface, and then a rust-proof treatment (CL8300) was performed. The copper foil etched with the microetchant is sometimes referred to as "CZ copper foil" below. Furthermore, the copper foil was heated in an oven at 130°C for 30 minutes to obtain a copper foil I having a roughened surface.

[0258] (2) Preparation of inner substrate A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, "R1515A" manufactured by Panasonic Corporation) having copper foil on the surface and formed with an inner layer circuit was prepared. Both sides of the glass cloth-based epoxy resin double-sided copper-clad laminate were etched by 1 μm with a microetchant ("CZ8101" manufactured by MEC Corporation) to roughen the copper foil surface. Thus, an inner layer substrate having a CZ copper foil with a treated surface on the surface was obtained.

[0259] (3) Lamination of resin composition layers The resin sheet A prepared in Test Example 1 (1) is laminated on both sides of the inner substrate. The lamination is performed using a batch vacuum pressure laminator (manufactured by Nikko-materials, a two-stage stacking laminator "CVP700") in such a way that the resin composition layer is in contact with the inner substrate. In addition, the lamination is performed by reducing the pressure for 30 seconds to adjust the air pressure to less than 13 hPa, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet is hot-pressed at 100°C and a pressure of 0.5 MPa for 60 seconds. Then, the support is peeled off to expose the resin composition layer.

[0260] (4) Lamination of copper foil and curing of resin composition layer Under the same conditions as in the above-mentioned "(3) Lamination of resin composition layer", the treated surface of copper foil I was laminated on the exposed resin composition layer. Then, the resin composition layer was cured under the curing conditions of 200°C and 90 minutes to form an insulating layer comprising a cured product of the resin composition. Through the above operation, an evaluation substrate C having CZ copper foil laminated on both sides of the insulating layer was obtained. The evaluation substrate C had a layer structure of copper foil I / insulating layer / inner substrate / insulating layer / copper foil I.

[0261] (5) Determination of copper foil peel strength The evaluation substrate C was cut into small pieces of 150 mm × 30 mm. In the small piece of copper foil I, a cutter was used to cut a cut that surrounded a portion with a width of 10 mm and a length of 100 mm. One end of the portion was peeled off and clamped with the clamp of a tensile testing machine (AUTOCOM universal testing machine "AC-50C-SL" manufactured by TSE). At room temperature (25°C), it was stretched in the vertical direction at a speed of 50 mm / min, and the load [kgf / cm] when peeling off 35 mm was measured as the copper foil peeling strength. The measurement was carried out in accordance with Japanese Industrial Standard JIS C 6481.

[0262] The measurement results of the test examples are summarized in Table 1 below.

[0263] [Table 1]

[0264] According to the results shown in Table 1, a cured product having low dielectric loss tangent and excellent mechanical strength and copper adhesion can be obtained by using the following resin composition; the resin composition comprises (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, wherein the content of the component (D) is 50% by mass or more when all non-volatile components in the resin composition are taken as 100% by mass, the maleimide group of the component (A) is 0.1 to 100 molar equivalents relative to 1 molar equivalent of the reactive group of the component (B), and the content of the epoxy resin (E) is 0 to 1% by mass when the non-volatile components other than the component (D) in the resin composition are taken as 100% by mass.

Claims

1. A resin composition comprising (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, in, When all nonvolatile components in the resin composition are set to 100% by mass, the content of the component (D) is 50% by mass or more. The maleimide groups of the component (A) are in an amount of 0.1 to 100 molar equivalents relative to 1 molar equivalent of the reactive groups of the component (B). When the nonvolatile matter other than the (D) component in the resin composition is 100% by mass, the content of the (E) epoxy resin is 0% by mass to 1% by mass.

2. The resin composition according to claim 1, wherein The maleimide group equivalent of the component (A) is 100 g / eq. to 500 g / eq.

3. The resin composition according to claim 1, wherein The component (A) comprises a maleimide resin selected from maleimide resins having a biphenyl skeleton, maleimide resins having an indane skeleton, maleimide resins having a bismaleimide diphenylmethane skeleton, maleimide resins having a carbon skeleton derived from dimer acid, and maleimide resins having an aromatic polyether ketone skeleton.

4. The resin composition according to claim 1, wherein When the nonvolatile matter other than the component (D) in the resin composition is taken as 100% by mass, the content of the component (A) is 30% by mass or more.

5. The resin composition according to claim 1, wherein The component (B) contains an anionic polymerizable curing agent selected from the group consisting of phenolic curing agents, carbodiimide curing agents, amine curing agents, benzoxazine curing agents, and active ester curing agents.

6. The resin composition according to claim 1, wherein The component (B) contains a phenolic curing agent.

7. The resin composition according to claim 1, wherein When the nonvolatile matter other than the component (D) in the resin composition is taken as 100% by mass, the content of the component (B) is 25% by mass or less.

8. The resin composition according to claim 1, wherein The mass ratio of the component (B) to the component (A), that is, the component (B) / component (A) is 0.05 to 1.

9. The resin composition according to claim 1, wherein When the nonvolatile matter other than the (D) component in the resin composition is 100% by mass, the content of the (C) component is 1% by mass to 5% by mass.

10. The resin composition according to claim 1, wherein The component (D) contains silicon dioxide.

11. The resin composition according to claim 1, wherein The present invention further comprises (F) a resin containing an ethylenically unsaturated bond.

12. The resin composition according to claim 1, wherein The composition further comprises (G) a thermoplastic resin.

13. The resin composition according to claim 1, wherein The cured product of the resin composition has a breaking strength of 100 MPa or more and a breaking elongation of 1.5% or more when the tensile strength is measured in accordance with JIS K7127.

14. The resin composition according to claim 1, wherein The glass transition temperature (Tg) of the cured product of the resin composition is 140° C. or higher.

15. The resin composition according to claim 1, wherein When measured under the conditions of 5.8 GHz and 23° C., the dielectric loss tangent (Df) of the cured product of the resin composition is 0.004 or less.

16. The resin composition according to claim 1, wherein When measured under the conditions of 5.8 GHz and 23° C., the relative dielectric constant (Dk) of the cured product of the resin composition is 3.2 or less.

17. A cured product of the resin composition according to any one of claims 1 to 16.

18. A resin sheet, wherein: A resin composition layer comprising a support and the resin composition according to any one of claims 1 to 16 and provided on the support.

19. A printed wiring board, wherein: An insulating layer is provided which is formed of a cured product of the resin composition according to any one of claims 1 to 16.

20. A semiconductor device, wherein: A printed wiring board comprising the method according to claim 19.

Citation Information

Patent Citations

  • Radiation control building

    JP1988079675A

  • Epoxy resin composition for semiconductor encapsulation, semiconductor device using the same, and semiconductor manufacturing method

    JP2014521754A